A contextual perspective on talented female participants and their development in extracurricular STEM programs - Stöger, Heidrun; Schirner, Sigrun; Lämmle, L; Obergriesser, S; Heilemann, M; Ziegler, Albert (Annals of the New York Academy of Sciences, 2016)

A Cross-Cultural Study of Implicit Theories of a Creative Person : Poster session presented at the International Conference on Talent Development & Excellence - Hopp, Manuel; Händel, Marion; Stöger, Heidrun; Ziegler, Albert (3rd International Conference on Talent Development and Excellence, 2013)

A cross-cultural study of implicit theories of an intelligent person - Aljughaiman, Abdullah; Duan, X; Händel, Marion; Hopp, Manuel; Stöger, Heidrun; Ziegler, Albert (Turkish Journal of Giftedness and Education, 2012)

A cross-cultural study of possible iatrogenic effects of gifted education programs: tenth graders´ perceptions of academically high performing classmates - Oh, Hyerim; Sutherland, Margaret; Stack, N; del Mar Badia, M; Blumen, S; Nguyen, Quoc Anh-Thu; Wormald, C; Maakrun, J; Ziegler, Albert (High ability studies, 2015)

A cross-cultural validation study of the Questionnaire of Educational and Learning Capital (QELC) in China, Germany and Turkey - Vladut, Anamaria; Liu, Q; Leana-Tasçilar, MarilenaZ.; Vialle, W; Ziegler, Albert (Psychological Test and Assessment Modeling, 2013)

A cross-national comparison of school students' perceptions regarding high performing peers - Oh, Hyerim; Sutherland, Margaret; Stack, N; del Mar Badia, M; Blumen, S; Nguyen, Quoc Anh-Thu; Wormald, C; Maakrun, J; Baier, B; Schmidt, M; Ziegler, Albert (Turkish Journal of Giftedness and Education, 2014)
UnivIS-Import:2015-03-09:Pub.2014.phil.dps.ipsy1.lpsych_2.across

A cross-national study of implicit theories of a creative person - Hopp, Manuel; Händel, Marion; Stöger, Heidrun; Vialle, Wilma; Ziegler, Albert (Education Sciences, 2016)

Actiotope model and self-regulated learning - Ziegler, Albert; Stöger, Heidrun (Psychological Test and Assessment Modeling, 2011)

Adolescent Perception of Potential High-Performing Classmates: A Cross-National Exploration - Oh, Hyerim; Sutherland, Margaret; Stack, Niamh; Badia Martín, Mar; Blumen, Sheyla; Nguyen, Quoc Anh Thu; Wormald, Catherine; Maakrun, Julie; Ziegler, Albert (Roeper review, 2019)
This study explores how secondary school students perceive high-performing potential classmates. A total of 1,794 seventh- and 10th-grade students from five countries completed a questionnaire measuring their expectations of hypothetical male and female high-performing classmates in three categories: intellectual ability, positive social qualities, and popularity. Across the five countries represented in this study, analyses of variance indicated that students did not report negative attitudes toward the three potential characteristics of a hypothetical gifted peer. Vietnamese students in particular reported more positive observations about the hypothetical classmate than their Australian, Peruvian, South Korean, and Spanish counterparts. Differing cross-national attitudes toward high-performing peers and the implications therein are discussed.
CRIS-Team Scopus Importer:2019-05-21
Keywords: high performing students; intellectual ability; peer perception; popularity; positive social qualities

Adolescents’ social perceptions of academically high-performing students: a country and gender comparative study - Oh, Hyerim; Sutherland, Margaret; Stack, Niamh; del Mar Badia Martín, Maria; Blumen, Sheyla; Nguyen, Quoc Anh Thu; Wormald, Catherine; Maakrun, Julie; Ziegler, Albert (Compare, 2019)
One cohort that has not been given extended attention in the period during which transition takes place is academically high-performing students. This research study uniquely synthesises some of these key factors by investigating how students in mixed-ability, seventh-grade classrooms across Australia, Peru, Scotland, South Korea, Spain and Vietnam regard a hypothetical, academically able peer. The fictitious student’s intellectual ability, positive social traits and popularity varied across the six countries involved in this study, and were observed according to the gender of the perceiver. More specifically, the perceived popularity of a high-performing boy or girl was reported differently among the country groups. In Scotland, for example, the authors uncovered a potential risk to female social status arising from peer reactions to her academic achievement. Yet in Vietnam, female study participants maintained a positive perception of both hypothetical students, regardless of gender. The results of this study are discussed herein.
CRIS-Team Scopus Importer:2019-05-21
Keywords: High performer; intellectual ability; peer perception; popularity; positive social qualities

Affektiv-motivational adaptive und handlungsadaptive Reaktionen auf Fehler im Lernprozess - Dresel, M.; Schober, B; Ziegler, Albert; Grassinger, Robert; Steuer, G (Zeitschrift für Pädagogische Psychologie, 2013)

Akademische Mediennutzung Studierender im Corona-Semester 2020 - Bedenlier, Svenja; Händel, Marion; Kammerl, Rudolf; Gläser-Zikuda, Michaela; Kopp, Bärbel; Ziegler, Albert (MedienPädagogik, 2021)
Unter dem Eindruck der CoViD-19 Pandemie erfolgte im Sommersemester 2020 an deutschen Hochschulen flächendeckende Online-Lehre im Notbetrieb. Die vorliegende längsschnittliche Fragebogenstudie untersucht die akademische Mediennutzung, -kompetenz und -ausstattung Studierender (N = 2.037) an einer deutschen Volluniversität zu Beginn und zur Mitte des betreffenden Semesters. Die Ergebnisse zeigen, dass die akademische Mediennutzung intensiviert wird, wahrgenommene digitale Kompetenzen der Studierenden zunehmen und E-Learning Angebote fakultätsspezifisch eingesetzt und genutzt werden. Sichtbar wird jedoch auch, dass Studierende mit heterogenen Voraussetzungen in das Semester starteten, die sich auch im Semesterverlauf auf die Studiensituation auswirkten. Die Ergebnisse werden vor dem Hintergrund bildungspolitischer Bestrebungen hinsichtlich der Digitalisierung der Hochschullehre, mediendidaktischer Fragestellungen und studentischem Eigensinn der Mediennutzung eingeordnet und diskutiert.
Keywords: Emergency Remote Teaching (ERT); Mediennutzung; Studierende; Hochschule

Aktiotop-Ansatz - Ziegler, Albert; Spann, Stefan (News & science, 2011)

Analysekategorien zur Bewertung von Lernumwelten: Soziotope und Bildungskapital - Ziegler, Albert (Hochbegabung, Exzellenz, Werte : Positionen in der schulischen Begabtenförderung, 2011)

Analyzing Barriers to Mentee Activity in a School-Based Talent Mentoring Program: A Mixed-Method Study - Daunicht, Tina-Myrica; Emmerdinger, Kathrin Johanna; Stoeger, Heidrun; Ziegler, Albert (Education Sciences, 2025)
Studies on talent development show that attaining expertise relies on long-term active engagement with a domain. Mentoring plays a key role in this, but it usually takes place outside of school in informal mentoring relationships, and research on formal school-based talent development mentoring programs is lacking. In the present research, we examined which factors in a novel school-based Learning Pathway Mentoring program hinder mentees’ active engagement with their domain. Due to a lack of corresponding research, we employed an exploratory sequential mixed-methods design (QUAL → quan). We first explored factors affecting mentees’ engagement from the perspective of 55 mentors in the Learning Pathway Mentoring program. The results of these qualitative analyses served to derive research questions about variables associated with decreased mentee domain activity, which we then studied in auxiliary quantitative analyses based on a sample of 48 mentees of the same program. Our combined analyses suggest that reasons for decreased mentee engagement may, in fact, be very heterogeneous and nuanced. As talent development places a significant demand on mentees in terms of extracurricular engagement, difficulties might occur specifically when mentees are expected to set priorities regarding the implementation of learning activities in their talent domain and simultaneously meet increasing school demands.
CRIS-Team Scopus Importer:2025-03-14
Keywords: engagement; mentoring; mixed method; motivation; talent development

An introduction to the special issue: A review of european and american perspectives and research on talent development - Subotnik, Rena F.; Stoeger, Heidrun; Assouline, Susan G.; Olszewski-Kubilius, Paula; Ziegler, Albert (Special Issue:The Future of Research in Talent Development: Promising Trends, Evidence, and Implications of Innovative Scholarship for Policy and Practice, 2019)
After a century during which the psychology of high ability focused largely on innate cognitive abilities, the twenty-first century ushered in a transfor-mative period in which views of talent broadened to include recognition that talent development is a much more complex process that begins with uncovering potential but does not stop there. Current approaches consider the whole process of talent development and include both individual and environmental aspects as well as their systemic interplay. Therefore, we can now document contributions of environmental, personal, psychosocial, educational, and chance factors to the cumulative conversion of potential abilities into high level performance or creativity. The eight contributions to this special issue flesh out various factors in the complex equation of talent development as it applies to different populations, contexts, and domains. One article addresses individual differences in abilities and how they can be measured and recognized. Another two focus on the peer group and how peers can influence creativity and acceptance. Three articles address factors of education and opportunity and how they affect the positive development of talent. One article identifies and categorizes the psychosocial skills needed for transforming potential into creative, productive achievement. A final paper addresses the place of talent development in the general developmental psychology literature.
CRIS-Team Scopus Importer:2019-11-29

A Nonagonal Framework of Regulation in Talent Development (NFRTD) - Ziegler, Albert; Stoeger, Heidrun (High ability studies, 2019)
Regulatory processes are pervasive on many levels in talent development, yet neither a systematic analysis of their role in talent development let alone a comprehensive model have been presented to date. The aim of this article is to demonstrate the diversity and complexity of regulatory processes in talent development and to provide a conceptual framework. The proposed nonagonal framework of regulation in talent development (NFRTD) distinguishes nine dimensions for the analysis of regulation in talent development: regulatory network (neutral, co-operative, competitive, hybrid, and panarchic), regulatory function (homeostasis and homeorhesis), control type (external, internal-automatic, and internal-controlled), regulatory type (open-loop control and closed-loop control), regulatory form (iterative and recursive), regulatory activities (preventive, detective, and corrective), regulated structures (exogenous and endogenous learning resources), regulatory side-effects (neutral, synergetic, destructive, catalytic, exploitative, and allostatic), and regulatory externalities (neutral, iatrogenic, and autocatalytic). The last section discusses the status of the nonagonal framework and hints at some fields of application.
CRIS-Team Scopus Importer:2019-05-21
Keywords: actiotope; educational capital; learning capital; Regulation; talent development

Are Competence Beliefs or Value Beliefs More Important for STEM Career Aspirations?—Longitudinal Mediation Analyses Based on Recent Modeling Approaches Show Different Results - Debatin, Tobias; Stoeger, Heidrun; Ziegler, Albert (Journal of Youth and Adolescence, 2025)
There is a consensus in situated expectancy-value theory research that value beliefs better predict career aspirations and choices than competence beliefs and thus should be the main target of interventions aimed to motivate youth for STEM (science, technology, engineering, math) careers. However, research on the longer-term causal effects of the two constructs and their indirect effects is missing. The latter is relevant since competence beliefs seem to influence value beliefs but less the other way around. The present study investigated such longer-term effects and the underlying indirect effects in a sample of 690 students from Germany (52.6% girls; M (T1) = 15.26 years, SD = 0.68) over three measurement points from the middle of Grade 9 to the middle of Grade 10. For these purposes, two recent models with improved properties for identifying causal effects, the random intercept cross-lagged panel model (RI-CLPM) and the dynamic panel model, as well as the traditional CLPM were applied. Final analyses were based on the RI-CLPM, and the results were compared to the traditional CLPM. Both models found the expected tendency of higher effects of STEM value beliefs on STEM career aspirations from one time point to the next. However, regarding the longer-term total effects, the analysis based on the RI-CLPM found a slight tendency for larger effects of competence beliefs, including an indirect effect of competence beliefs via value beliefs. These findings indicate that the competence beliefs of youth should not be underestimated in developing interventions for career aspirations and choices.
CRIS-Team Scopus Importer:2025-03-21
Keywords: Academic self-concept; Career aspirations; Competence beliefs; STEM; Value beliefs

Are gifted students more emotionally intelligent than their non-gifted peers? A meta-analysis - Abdulla Alabbasi, Ahmed M.; Alaa, Alaa Eldin; Ziegler, Albert (High ability studies, 2020)
This Meta-Analysis investigated the relationship between emotional intelligence (EI) and giftedness. The study focused on whether gifted learners possessed higher levels of EI when compared with their non-gifted peers. Furthermore, it sought to determine if gifted males and gifted females differed in their EI abilities. A search of published and unpublished studies in English and Arabic from 1990 to 2018 resulted in 21 studies that compared gifted with non-gifted students, and 11 studies that compared gifted males with gifted females in their EI ability. Using a random-effect model, the results showed that gifted students outperformed non-gifted students on EI, g = 0.226, SE =.036, 95% CI [0.155, 0.297], p <.001. Furthermore, gifted females significantly surpassed gifted males in regrades to their emotional intelligence, g = 0.164, SE =.046, 95% CI [0.074, 0.255], p <.001. Multiple regression analyses showed that age, gender, EI measures, and EI skills significantly explained 18% of the variability in the mean effect between gifted vs. non-gifted students; whereas the age and EI skills moderators significantly explained 49% of the variation in the mean effect between gifted male and gifted female students. Implications and future directions were discussed.
CRIS-Team Scopus Importer:2020-06-23
Keywords: emotional intelligence; gender differences; Gifted; meta-analysis; non-gifted

Are pupils with differing cognitive abilities able to profit similarly from training to mediate self-regulated learning and homework skills? - Stöger, Heidrun; Ziegler, Albert (Gifted education international, 2010)
UnivIS-Import:2015-03-09:Pub.2010.phil.dps.ipsy1.lpsych_2.arepup

Attracting and developing STEMM talent toward excellence and innovation - Stoeger, Heidrun; Luo, Linlin; Ziegler, Albert (Annals of the New York Academy of Sciences, 2024)
This article provides an overview of science, technology, engineering, mathematics, and medical sciences (STEMM) talent development from first exposure to a STEMM domain to achieving eminence and innovation. To this end, a resource-oriented model of STEMM talent development is proposed as a framework. It includes a three-stage phase model based on Bloom (1985), with the main focus on interest development in the first stage, skill acquisition toward expertise and excellence in the second stage, and style formation toward eminence and innovation in the final stage. A literature review shows that from an educational perspective, each phase is mainly characterized by the focus that Bloom postulated. However, it is important that all three stages (i.e., interest development, skill acquisition, and style formation) occur in a stage-typical manner. To explain how these primary objectives of STEMM development can be supported through STEMM talent education, Ziegler and Stoeger's (2011) educational and learning capital framework is used in the proposed resource-based model. A literature review shows that consistent provisioning of the resources specified in the model is necessary for individuals to complete a learning pathway to STEMM eminence and innovation.
CRIS-Team Scopus Importer:2024-03-22
Keywords: educational capital; innovation; learning capital; learning resources; STEMM; talent development

Begabende Umwelten, begabte Personen. Ein Plädoyer für eine ganzheitliche Begabungsidentifikation. - Harder, Bettina; Trottler, Susanne; Ziegler, Albert (News & science, 2014)

Begabtenförderung aus einer systemischen Perspektive - Stöger, Heidrun; Ziegler, Albert (Journal für Begabtenförderung, 2009)
UnivIS-Import:2015-03-09:Pub.2009.phil.dps.ipsy1.lpsych_2.begabt

Begabtenförderung und Lernumwelten: Soziotope als Rahmenbedingungen der MINT-Förderung von Mädchen und Frauen - Reutlinger, Marold; Buschhaus, F; Groß, C; Hopp, Manuel; Werner, K; Ziegler, Albert (Handbuch der Entwicklungspsychologie des Talents, 2014)
UnivIS-Import:2015-04-20:Pub.2014.phil.dps.ipsy1.lpsych_2.begabt

Begabungs-, Expertise- und Innovationsforschung - Ziegler, Albert; Grassinger, Robert; Harder, Bettina (News & science, 2008)
UnivIS-Import:2015-03-09:Pub.2008.phil.dps.ipsy1.lpsych_2.begabu

Begabungsförderung aus einer systemischen Perspektive - Ziegler, Albert; Stöger, Heidrun (Journal für Begabtenförderung, 2009)

Bildungskapital. Eine ergänzende Perspektive auf die Entwicklung von Leistungsexzellenz - Ziegler, Albert; Murat, A (News & science, 2011)

Bildungskapital und die Förderung von Lernsoziotopen - Ziegler, Albert (Individuelle Förderung multipler Begabungen, 2012)

Bildungsökonomie - Ziegler, Albert (Realschule in Deutschland, 2009)

Bildungspsychologische Forschung - Händel, Marion; Ziegler, Albert (Bildungspsychologie, 2022)

Bildungspsychologische Forschung - Ziegler, Albert (Bildungspsychologie, 2010)

Bildungs- und Lernkapitalarmut von Hauptschülern: Ergebnisse einer explorativen Befragungsstudie mit Lehrkräften - Ziegler, Albert; Hopp, Manuel; Linner, Markus; Schöferle, Tanja; Thomas, Niklas; Schielein, Tanja; Vladut, Anamaria; Götzfried, Wolfgang (Schulpädagogik-heute, 2012)

Bildungs- und Lernkapitalarmut von Hauptschülern: Ergebnisse einer explorativen Befragungsstudie mit Lehrkräften - Ziegler, Albert; Hopp, Manuel; Linner, Markus; Schöferle, Tanja; Thomas, Niklas; Schielein, Tanja; Vladut, Anamaria; Götzfried, Wolfgang (Schulpädagogik heute, 2012)

Bildungs- und Lernkapital - Ziegler, Albert; Stöger, Heidrun; Vladut, Anamaria; Zirkelbach, Doris (Giftedness Across the Lifespan – Begabungsförderung von der frühen Kindheit bis ins Alter. Forder- und Förderkonzepte aus der Forschung, 2015)

Bildungs- und Lernkapital. Ein ressourcenorientierter Ansatz - Ziegler, Albert; Stöger, Heidrun (Journal für Begabtenförderung, 2013)

Bildungs- und Lernkapital [Special Issue] - Harder, Bettina; Stöger, Heidrun; Ziegler, Albert (Journal für Begabtenförderung, 2013)

Bildungs- und Lernkapital. Tagungsbeitrag auf dem 4. Münsterschen Bildungskongress - Ziegler, Albert; Stöger, Heidrun; Vladut, Anamaria; Zirkelbach, Doris (2012)

CAN EMINENCE IN STEAM PRODUCE MORE FEMALE ROLE MODELS? RECENT TRENDS IN PRIZES KNOWN AS THE NOBEL OR THE HIGHEST HONORS OF A FIELD - Nunez, Miguelina; Yu, Hsiao Ping; Ziegler, Albert (Contemporary Educational Research Quarterly, 2023)
Purpose In many STEM fields, the intersectionality of gender and excellence is a frequently noted phenomenon, i.e., women are underrepresented in STEM in general and specifically, at the top. Role models presumably play a key part in closing this equity gap. However, these are not available in sufficient numbers. Many researchers have suggested better outreach to female talents by integrating the arts into STEAM. One possibility might be that such an integration would make more female role models available to STEAM talent pools. (82) Design/methodology/approach We explored the availability of potential role models for female talents by analysing the ten most prestigious awards in STEM and the arts over the past 42-plus years using a 2 X 2 X 2 X 10 hierarchical log-linear analysis. Variables were gender (female vs. male), award type (STEM or arts), award (ten different awards per award type), and time period (1980–2000 vs 2001–2021). Three research questions were investigated: (1) whether and to what extent gender gaps exist in Nobel Prizes and prizes known as the Nobel, or the highest honors of a field in STEM and in the arts, (2) whether gender gaps in Nobel Prizes and prizes known as the Nobel or the highest honors are equally distributed across individual STEM fields and across the individual arts domains, and (3) what trends emerge in the recipient pool of Nobel Prize winners and winners of prizes known as the Nobel or the highest honors. (156) Findings/results First, women do receive substantially fewer of the top awards, with a slightly larger gender gap in STEM than in the arts. Second, findings showed large differences in the probabilities with which each STEM or arts prize was awarded to women. Thus, differences emerge not only between STEM and the arts, but also within STEM and arts awards. Third, there were comparable significant increases in awards to women in both STEM and the arts after the turn of the millennium. Originality/value The prizes explored in this study were awarded between 1980 and 2021. Future researchers should explore whether the gains made at the turn of the millennium for female talent pools have or are in the process of calcifying as of the publication date of this article. While the researchers of this study did not focus on the nomination pool, a cursory look at 100 years of Academy Award nominations reveals that female talent was not being considered, and thus could not be awarded. Does this extend to the nomination pools of other eminence prizes? Additionally, there are still far too few non-stereotypical, female role models at the top tiers of arts domains that might “inoculate” against the male STEM stereotype. If the introduction of male talent into female gender-typed work or ‘women’s work’ produces ever more eminence prizes for male talent, then a question of quality control has been raised and should be leveraged against talent pools, particularly in the STEM/STEAM domains where male talent dominates. Implications for policy/practice Introducing arts into STEM is not enough to bridge the achievement gender gap. Future studies might focus on whether eminence prizes are appropriate end-points of career development, particularly in the context of female talent development in STEM/STEAM fields. Moreover, this paper discussed the effect of gender concurrence and eminence prizes: the effect of female role models on women. However, this effect can also extend to male talent pools. Future research on the effects of successful female role models in STEAM should therefore include effects on boys.
CRIS-Team Scopus Importer:2023-12-22
Keywords: arts; gender; Nobel Prize; role model; STEAM; STEM; talent development

Chinas Erfolg bei PISA: Zufall oder Artefakt - Ziegler, Albert; Harder, Bettina; Trottler, Susanne (Labyrinth, 2014)

Competencies for successful self-regulated learning in higher education: structural model and indications drawn from expert interviews - Dresel, Markus; Schmitz, Bernhard; Schober, Barbara; Spiel, Christiane; Ziegler, Albert; Engelschalk, Tobias; Jöstl, Gregor; Klug, Julia; Roth, Anne; Wimmer, Bastian; Steuer, Gabriele (Studies in Higher Education, 2015)
<!–StartFragment–>A global characteristic of higher education is the opportunity and necessity for students to self-regulate their learning. In contrast to considerable research focusing on self-regulated learning (SRL) from a behavioural perspective, little is known concerning the underlying competencies which enable students to succeed in SRL. A structural model is proposed that differentiates SRL competencies in terms of descriptive, procedural, and conditional knowledge regarding different types of self-regulation strategies in different phases of the learning process. Indications drawn from semi-structured interviews with N = 108 experts (39 lecturers and 69 as excellent nominated students) from 4 fields of study are in line with core assumptions of the proposed model. Moreover, the results provide a basis to ensure the content validity of assessments of students' SRL competencies and from which to derive standards to judge these competencies.<!–EndFragment–>
Keywords: competencies; expert interviews; learning situations

Correspondence Heuristic and Filter-Empowerment Heuristic: Investigating the Reversed Gender Achievement Gap in a Sample of Secondary School Students in Saudi Arabia within the Framework of Educational and Learning Capital - Stoeger, Heidrun; Almulhim, Norah; Ziegler, Albert (Education Sciences, 2022)
The reversed gender achievement gap in the Kingdom of Saudi Arabia (KSA) in favor of girls developed in a societal environment that still predominantly favors men. The finding illustrates how equity gaps at higher systemic levels may not translate seamlessly to lower systemic levels. We propose that this lack of correspondence between systemic levels regarding equity gaps can be explained by the fact that more exogenous learning resources (educational capital) selectively reach girls' actiotopes, enabling them to build more effective endogenous learning resources (learning capital) and, in particular, effective action repertoires. To investigate this assumption, we introduce a filter-empowerment heuristic and contrast it with a simpler correspondence heuristic. We employ the filter-empowerment heuristic and the education and learning capital approach to investigate the reversed gender achievement gap in a sample of secondary school students in the KSA. We test four hypotheses: (a) Girls have higher academic achievement than boys. (b) Girls have more educational capital and (c) more learning capital than boys. (d) Educational and learning capital mediate the relationship between gender and academic achievement. The hypotheses were tested with a sample of 2541 ninth-grade students from 55 KSA schools. The four hypotheses were confirmed and support a filter-empowerment heuristic rather than a correspondence heuristic.
CRIS-Team WoS Importer:2022-12-23

Corrigendum: The effects of inhibitory control training for preschoolers on reasoning ability and neural activity - Liu, Q; Shi, Jiannong; Ziegler, Albert (Scientific Reports, 2016)

Creative, thus connected: The power of sociometric creativity on friendship formation in gifted adolescents—a longitudinal network analysis of gifted students - Hopp, Manuel; Zhang, Zhitian; Hinch, Leeanne; O’reilly, Colm; Ziegler, Albert (Special Issue:The Future of Research in Talent Development: Promising Trends, Evidence, and Implications of Innovative Scholarship for Policy and Practice, 2019)
The current study’s purpose is to explore the influence of peer-perceived creativity (sociometric creativity) on the short-term development of friendships during a summer program for high ability students. Specifically, the two main objectives of our study are: (1) How did students’ friendships network and sociometric creativity network evolve in the summer program? (2) How did sociometric creativity influence the friendship formation? The longitudinal study was conducted at the beginning, middle and the end of a 3-week long program for gifted students in Ireland. The sample consisted of Irish gifted students (N = 702, aged 13–18 years, 52% female, over thirty-one classes). Overall, our longitudinal multilevel and multigroup social network analysis shows that gifted adolescents formed reciprocated friendship ties and cohesive peer group structures in the investigated period; similar age and the same gender predicted friendship formation. Regarding the sociometric creativity, they tended to nominate a similar age and same gender student as very creative. Moreover, the sociometric creativity positively influenced adolescents’ friendship networks on a dyadic level, indicating that adolescents select friends based on their perception of the other student’s creativity. Further results, explanations, and implications are discussed.
CRIS-Team Scopus Importer:2019-11-29

(untitled) - Stöger, Heidrun; Sturm, K; Heilemann, M; Pufke, E; Schirner, Sigrun; Reutlinger, Marold; Ziegler, Albert (Österreichisches Zentrum für Begabtenförderung und Begabungsforschung)

CyberMentor: E-Mentoring für begabte Mädchen in MINT - Ziegler, Albert; Stöger, Heidrun; Sturm, K; Heilemann, M; Pufke, E; Schirner, Sigrun; Reutlinger, Marold (Begabung - Wissen - Werte : Wege zur Leistungsexzellenz, 2011)

CyberMentor - E-Mentoring für Mädchen im MINT-Bereich vor dem Hintergrund des Aktiotopansatzes - Stöger, Heidrun; Ziegler, Albert; Greindl, Teresa; Heilemann, M; Neubauer, Tanja; Schirner, Sigrun; Sturm, K (Druck Team, 2014)
UnivIS-Import:2015-04-02:Pub.2014.phil.dps.ipsy1.lpsych_2.cyberm

Das Beratungskonzept der Landesweiten Beratungs- und Forschungsstelle für Hochbegabung (LBFH) - Ziegler, Albert; Grassinger, Robert; Stöger, Heidrun; Harder, Bettina (Konzepte der Hochbegabtenberatung in der Praxis, 2012)

Das Lernpfadkonzept: Theoretischer Hintergrund und zentrale Konzepte. - Ziegler, Albert; Daunicht, Tina-Myrica; Quarda-Häußler, Ann-Kathrin; Emmerdinger, Kathrin J; Stoeger, Heidrun (Dimensionen der Begabungs- und Begabtenförderung in der Schule, 2022)

Deficits in fine motor skills and its influence on persistence among gifted elementary school pupils - Stöger, Heidrun; Ziegler, Albert (Gifted education international, 2013)

Der Soziotop-Ansatz in der Begabungsförderung: Theoretischer Hintergrund und Anwendungsperspektiven - Ziegler, Albert; Stöger, Heidrun (Journal für Begabtenförderung, 2016)

Development of excellence in East-Asia: Explorations in the Actiotope model of giftedness - Phillipson, Sivanes; Stöger, Heidrun; Ziegler, Albert (Routledge, 2012)
UnivIS-Import:2015-04-02:Pub.2012.phil.dps.ipsy1.lpsych_2.develo

Development of excellence in East-Asia: Explorations in the Actiotope model of giftedness - Phillipson, S; Stöger, Heidrun; Ziegler, Albert (Routledge, 2012)
UnivIS-Import:2015-05-08:Pub.2012.phil.dps.ipsy1.lpsych_2.talent

Diagnosing resources for effective learning via teacher and parent checklists - Harder, Bettina; Trottler, Susanne; Vialle, Wilma; Ziegler, Albert (Psychological Test and Assessment Modeling, 2015)

Diagnosis of self-regulated learning profiles - Ziegler, Albert; Stöger, Heidrun; Vialle, W; Wimmer, Bastian (Australasian journal of gifted education, 2012)

Diagnostik selbstregulierten Lernens mit dem Fragebogen SelstReguliertes Lernen-7 - Ziegler, Albert; Stöger, Heidrun; Grassinger, Robert (Journal für Begabtenförderung, 2010)
UnivIS-Import:2015-03-09:Pub.2010.phil.dps.ipsy1.lpsych_2.diagno

Diagnostik selbstregulierten Lernens mit dem FSL-7 - Ziegler, Albert; Stöger, Heidrun; Grassinger, Robert (Journal für Begabtenförderung, 2010)

Die Entwicklung der Nürnberger Bildungs- und Lernkapital-Checkliste (NBLC) - Harder, Bettina; Trottler, Susanne; Ziegler, Albert (Journal für Begabtenförderung, 2013)

Die Konzeption der Landesweiten Beratungs- und Forschungsstelle für Hochbegabung (LBFH) - Trottler, Susanne; Harder, Bettina; Ziegler, Albert (4. Münsterschen Bildungskongress, 2012)

Die Verwendung von Begabung, Talent und Hochbegabung in der deutschen Sprache - Ergebnisse einer korpuslinguistischen Untersuchung - Balestrini, Daniel Patrick; Harder, Bettina; Stöger, Heidrun; Ziegler, Albert (Labyrinth, 2013)

Digital readiness and its effects on higher education students’ socio-emotional perceptions in the context of the COVID-19 pandemic - Händel, Marion; Stephan, Melanie; Gläser-Zikuda, Michaela; Kopp, Bärbel; Bedenlier, Svenja; Ziegler, Albert (Journal of Research on Technology in Education, 2020)
The current study investigated how ready higher education students were for emergency remote teaching due to the COVID-19 pandemic and how this influenced their socio-emotional perceptions. Results of N = 1,826 higher education students indicate that they seem to be ready for digital learning. A k-means cluster analysis revealed two groups of students that significantly differed with respect to their readiness for digital learning (in terms of technology equipment availability, prior experiences with e-learning, and skills for digital learning). Finally, students’ socio-emotional perceptions, that is, stress-related emotions (worries, tension, joy, and overload) as well as social and emotional loneliness significantly differed due to cluster membership. Hence, the study points a need for support of higher education students in successfully coping with the challenges of emergency remote studying.

Digital readiness and its effects on higher education students’ socio-emotional perceptions in the context of the COVID-19 pandemic - Händel, Marion; Stephan, Melanie; Gläser-Zikuda, Michaela; Kopp, Bärbel; Bedenlier, Svenja; Ziegler, Albert (Journal of Research on Technology in Education, 2022)

Does fluid intelligence facilitate the learning of English as a foreign language?-A longitudinal latent growth curve analysis - Debatin, Tobias; Harder, Bettina; Ziegler, Albert (Learning and individual differences, 2019)
The relationship between intelligence and learning is still a controversial topic. The study at hand examined, via growth curve analysis, if fluid intelligence predicts long-term learning rates of foreign language acquisition in English. From the beginning of grade 5 to the middle of grade 7, N = 521 students were tested four times with Rasch-scaled English achievement tests. Intrinsic motivation was measured as a control variable. Fluid intelligence and intrinsic motivation were found to be related to the initial level of English achievement. However, neither fluid intelligence nor intrinsic motivation predicted the rate of change concerning the English scores. These findings extend the growing body of evidence that the relation between intelligence and rate of academic long-term learning may not be as strong as traditionally expected.
CRIS-Team WoS Importer:2019-04-16

Do higher education students have the means to learn during the Covid-19 pandemic? Student demands for distance learning in a suddenly digital landscape - Händel, Marion; Bedenlier, Svenja; Gläser-Zikuda, Michaela; Kammerl, Rudolf; Kopp, Bärbel; Ziegler, Albert (Journal for Educational Research Online, 2022)
Across the globe, 2020 terms began under conditions incited by the corona pandemic. Within a relatively short amount of time, universities started to develop and implement online courses for distance learning. These changes in learning and teaching may well have been a challenge for students.The current study is about an online survey at a German full-scale university investigating the unique circumstances under which students began the digital 2020 summer term. Of approximately 38,500 students, N = 5,563 students from across all institutional faculties took part in the survey. Results indicate how well students are equipped with devices for digital learning; what kind of experiences they have already made with online learning; and how competent they reported feeling regarding digital learning. Moreover, group differences between faculties, degrees, and gender were investigated. The study provides important insights into digital higher education during the exceptional pandemic situation. The results are intended to feed into student counselling systems via support by way of access to devices or courses regarding digital key competences, or through counselling for students with special social burden
Keywords: higher education; E-Learning; ICT skills; corona pandemic

Do Higher Education Students Have the Means to Learn During the COVID-19 Pandemic? Student Demands for Distance Learning in a Suddenly Digital Landscape - Händel, Marion; Bedenlier, Svenja; Gläser-Zikuda, Michaela; Kammerl, Rudolf; Kopp, Bärbel; Ziegler, Albert (Journal for Educational Research Online, 2022)
Across the globe, 2020 terms began under conditions incited by the corona pandemic. Within a relatively short amount of time, universities started to develop and implement online courses for distance learning. The current study is about an online survey at a German university investigating the unique circumstances under which students began the digital 2020 summer term. Of approximately 38 500 students, N = 5563 students from across all institutional faculties took part in the survey. Results indicate how well students are equipped with devices for digital learning, what kind of experiences they have already made with online learning, and how competent they reported feeling regarding digital learning. The study provides important insights into digital higher education during the exceptional pandemic situation. The results are intended to feed into student counselling systems via support by way of access to devices or courses regarding digital skills, or through counselling for students with special social burdens.
CRIS-Team WoS Importer:2022-07-22

Domain-Specificity of Educational and Learning Capital: A Study With Musical Talents - Reutlinger, Marold; Pfeiffer, Wolfgang; Stoeger, Heidrun; Vialle, Wilma; Ziegler, Albert (Frontiers in Psychology, 2020)
The Education and Learning Capital Approach (ELCA) has been widely used to investigate talent development. A research gap is the implicit consideration of the domain specificity of educational and learning capital. In an empirical study with 365 school students we investigated the domain specificity of the approach for the domains of school learning and learning to play a musical instrument. At the beginning of the school year, students filled out a version of the Questionnaire for Educational and Learning Capital (QELC) for both domains and also responded to other domain-related measures (self-efficacy, grades). Six weeks later, students filled out a learning diary for 1 week in which they reported their activities on an hourly basis and responded to questions concerning these activities. Based on the Sociotope Approach this procedure helped to identify times in which students actually practiced their musical instrument, times that students could potentially practice their musical instrument (objective action space), and times that students would be expected to practice their musical instrument (normative action space). Three hypotheses were tested and could be supported. First, the availability of educational and learning capital for school learning and learning an instrument differed. Second, a confirmatory factor analysis supported the factorial validity of the domain-specific capital measurements. Third, domain-congruent correlations were mostly higher than domain-incongruent correlations, i.e., the availability of educational and learning capital for school learning correlated more closely with variables related to school learning than with variables related to learning a musical instrument. Similarly, the availability of the capitals for learning a musical instrument correlated more closely with variables related to learning a musical instrument.
CRIS-Team Scopus Importer:2020-10-23
Keywords: domain specificity; educational capital; learning capital; music; talent development

Domänenspezifische Replikation der Studie von Mueller und Dweck (1998) zur negativen Wirkung von Entitätsfeedback - Steinbach, J; Harder, Bettina; Stöger, Heidrun; Ziegler, Albert (47. Kongress der Deutschen Gesellschaft für Psychologie, 2010)

Do Pupils with Differing Cognitive Abilities Benefit Similarly from a Self-Regulated Learning Training Program? - Ziegler, Albert; Stöger, Heidrun (Gifted education international, 2010)

Dropping out of an online mentoring program for girls in STEM: A longitudinal study on the dynamically changing risk for premature match closure - Uebler, Claudia; Emmerdinger, Kathrin J.; Ziegler, Albert; Stoeger, Heidrun (Journal of Community Psychology, 2023)
Premature closure of mentoring relationships decreases positive effects of mentoring or can even lead to negative effects for mentees. Past studies retrospectively investigated mechanisms of premature match closure. However, a deeper understanding of the dynamics that lead to premature match closure is still missing. In our study, we longitudinally examined the preprogram characteristics, program adherence, as well as program communication and networking behavior of girls (N = 901, M = 13.80 years) who took part in a 1-year online mentoring program in science, technology, engineering and mathematics (STEM), comparing girls who dropped out of the program prematurely (N = 598) with girls who were considered as non-dropouts (N = 303). We used survival analysis methods to simultaneously analyze time-independent characteristics and time-dependent dynamics of mentees' communication and networking behavior. Besides mentees' interest in STEM and compliance with program specifications, a frequent and steady communication with their mentors decreased the risk for premature match closure, especially, if it focused on STEM. Mentors' mentoring experience, mentees' program-wide networking and their networking with other mentees reduced the risk for premature match closure. Regarding the STEM focus of networking, we found competing influences, which need to be further explored in future research.
CRIS-Team Scopus Importer:2023-04-14
Keywords: girls in STEM; longitudinal study; online mentoring; premature match closure; survival analysis

Dynamische EduSpaces - Ziegler, Albert; Harder, Bettina; Arndt, H (Theoretische Perspektiven der modernen Pädagogik, 2014)
UnivIS-Import:2015-04-20:Pub.2014.phil.dps.ipsy1.lpsych_2.dynami

Dynamische Edu Spaces - Ziegler, Albert; Harder, Bettina; Arndt, Holger (Reform und Innovation - Beiträge pädagogischer Forschung, 2014)

Editorial: Advanced Learning - Vialle, Wilma; Stoeger, Heidrun; Ziegler, Albert (Frontiers in Psychology, 2021)
CRIS-Team WoS Importer:2021-07-23

Editorial - Ziegler, Albert (High ability studies, 2016)

Educational and learning capital of a world champion - Ziegler, Albert; Vladut, Anamaria; Leavitt, M.; Speckenheuer, R. (Talent Talks, 2012)

Embodiment: I sat, I felt, I performed – Posture effects on mood and cognitive performance - Awad, Sarah; Debatin, Tobias; Ziegler, Albert (Acta Psychologica, 2021)
Previous embodiment findings indicate a relationship between physical posture and mood states, suggesting upright postures induce positive mood states. Findings also showed a relationship between moods and cognitive performance. While positive mood states were found to be related to increased processing speed, negative mood states were associated with higher processing accuracy in cognitive task performance. This implies that posture may affect the aforementioned sub-aspects of cognitive performance via mood states. Additionally, most studies on posture effects rely on explicit posture manipulation. With that in mind, our research explores the effects of implicitly manipulated postures on processing speed and accuracy and whether these effects are mediated by general mood. The results revealed that subjects in our sample (N = 82, M = 23.09 years) who adopted an upright posture showed a more positive general mood (d = 0.50) and higher processing speed (d = 0.42) compared to those in stooped postures. Surprisingly, no differences in processing accuracy were found. There was no evidence of the proposed mediation in our data.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Embodied cognition; General mood; Posture; Processing accuracy; Processing speed

E-portfolio use and its effects on exam performance–a field study - Händel, Marion; Wimmer, B.; Ziegler, Albert (Studies in Higher Education, 2018)
Keywords: field study; E-portfolio; performance; learning strategies; teacher education

Equity Gaps in Education: Nine Points toward More Transparency - Ziegler, Albert; Kuo, Ching-Chih; Eu, Sen-Peng; Gläser-Zikuda, Michaela; Nunez, Miguelina; Yu, Hsiao-Ping; Harder, Bettina (Education Sciences, 2021)
The aim of this paper is to increase transparency in the scientific analysis of equity gaps in education. This should be useful in avoiding common ambiguities and misunderstandings in the discourse and in presenting the analyses results in a constructive way. We focused on a very basic aspect of transparency: Information availability. We identified nine topics related to the constitutive terms: "equity", "gap", and "education", topics for which information is often only implicitly or selectively transmitted or not transmitted at all. Regarding the constitutive term "equity", and as the possible sources of transparency problems, we analyzed (1) the type of equity model, (2) the underlying distribution model, and (3) the group concept between which equity gaps exist. For the clarification of the constitutive term "gap", we addressed (4) the applicability issue, (5) the indicator issue, (6) the reference issue, and (7) the significance issue. The last two sources of transparency problems were related to the constitutive term "education" and referred to (8) the location of the equity gap within or outside education and (9) the characterization of the equity gap within education. For each of the nine topics, we highlight the biggest problems of understanding and propose solutions.
CRIS-Team WoS Importer:2021-12-17

Equity Gaps in Literacy among Elementary School Students from Two Countries: The Negative Social Resonance Effect of Intersectional Disadvantage and the Dampening Effect of Learning Capital - Ziegler, Albert; Luo, Linlin; Stoeger, Heidrun (Education Sciences, 2023)
Students may be members of multiple disadvantaged groups whose negative effects may reinforce each other (intersectionality). In two studies dealing with elementary students’ literacy skills, we examine one negative reinforcing effect and one dampening effect of intersectionality. In Study 1, we tested the negative social resonance effect of intersectional disadvantage, which means that disadvantages in achievement of intersecting disadvantaged groups would be stronger in social judgments of achievement than in objective measurement. This assumption was confirmed with a sample of 1926 German fourth-grade students. A MANOVA showed that the disadvantages in SES, migration background, and gender were cumulative. A path analysis revealed that the negative effects were larger in teachers’ performance assessments than in objective test performance in literacy. In Study 2, the negative social resonance effect of intersectional disadvantage was replicated with a sample of 777 students from Grades 4 and 5 in the United Arab Emirates. In addition, a dampening effect of learning capital was found. This effect was comparatively larger than the negative social resonance effect of intersectional disadvantage.
CRIS-Team Scopus Importer:2023-09-08
Keywords: dampening effect; educational capital; intersectionality; learning capital; literacy; social resonance effect

Erfolgreich in MINT: Mentoring für Mädchen und Frauen - Stöger, Heidrun; Ziegler, Albert; Greindl, Teresa; Heilemann, M; Neubauer, Tanja; Reutlinger, Marold; Schirner, Sigrun; Sturm, K (Häuser, 2012)
UnivIS-Import:2015-04-02:Pub.2012.phil.dps.ipsy1.lpsych_2.erfolg

Erste Schritte zu einer systemischen Begabungsdiagnostik: Ein Paradigmenwechsel von der Potenzialfeststellung zur Exzellenzvorhersage - Stöger, Heidrun; Debatin, Tobias; Ziegler, Albert (Begabungen und Talente (Tests und Trends - Jahrbuch der pädagogisch-psychologischen Diagnostik, 2017)

Evaluating the Effectiveness of Social Visualization within Virtual Communities - Schimke, Diana; Stöger, Heidrun; Ziegler, Albert (Virtual Communities of Practice and Social Interactive Technologies: Lifecycle and Workflow Analysis, 2009)
UnivIS-Import:2015-04-20:Pub.2009.phil.dps.ipsy1.lpsych_2.evalua

Evaluating the use of social visualization within virtual communities - Ziegler, Albert; Schimke, Diana; Stöger, Heidrun (Virtual community practices and social interactive media : technology lifecycle and workflow analysis, 2009)

Excellence among older people: A resource-oriented approach - Ziegler, Albert; Liu, Q; Wimmer, Bastian; Sutherland, Margaret (Talent development & excellence, 2013)

Excellence - Ziegler, Albert; Perleth, C (LIT, 2011)
UnivIS-Import:2015-04-02:Pub.2011.phil.dps.ipsy1.lpsych_2.excell

Excellence : essays in honour of Kurt A. Heller - Ziegler, Albert; Perleth, C (Lit, 2011)

Exceptionality and gifted education: a re-examination of its hard core - Ziegler, Albert; Phillipson, Shane N (High ability studies, 2012)

Exceptionality in East Asia : explorations in the actiotope model of giftedness - Phillipson, Shane N; Stöger, Heidrun; Ziegler, Albert (Routledge, 2013)

Exogenous and endogenous learning resources in the Actiotope Model of Giftedness and its significance for gifted education - Ziegler, Albert; Chandler, K; Vialle, W; Stöger, Heidrun (Journal for the education of the gifted, 2016)

Expertisierung als Adaptions- und Regulationsprozess: Die Rolle von Bildungs- und Lernkapital - Ziegler, Albert; Stöger, Heidrun (Motivation, Selbstregulation und Leistungsexzellenz, 2011)

Extending Research on Psychosocial Skills and Appropriate Instruction in Developing Talents - Olszewski-Kubilius, Paula; Subotnik, Rena F.; Worrell, Frank C.; Assouline, Susan G.; Stoeger, Heidrun; Ziegler, Albert (Journal for the education of the gifted, 2024)
CRIS-Team Scopus Importer:2024-09-27
Keywords: Appropriate instruction; Psychosocial skills; Talent development

Female top performers in higher education STEM and humanities: socio-emotional perceptions and digital learning-related characteristics during COVID-19 - Ziegler, Albert; Bedenlier, Svenja; Gläser-Zikuda, Michaela; Kopp, Bärbel; Händel, Marion (Journal for the Education of Gifted Young Scientists, 2020)
In Germany, the 2020 summer semester was substantially influenced by the COVID-19 pandemic. In an empirical study, we focus on female top performing students in STEM and the humanities. Of particular interest was whether the measures associated with the pandemic constitute a risk-factor for a re-traditionalization of gender roles. Before lectures or courses began, students at a full-scale university were invited to participate in an online survey. We investigated four research questions: 1) Are women underrepresented in our sample among the top performers in STEM and the humanities? Are there gender differences among top performers with regard to (2) digital readiness, (3) socio-emotional and (4) learning related variables? The sample of the study consisted of 2,849 higher education STEM and humanities students. The study took place as an online survey. In the week before the start of the official lecture period, all students enrolled at the university were invited to take part via an e-mail correspondence from the Vice President of Education (survey access link). Participation in the survey took place via the Questback platform and was activated for 10 days. The cut-off point for the ability level was set at the 95th percentile of previous university achievements. To test Q1, we performed a hierarchical loglinear analysis with posthoc Chi² tests. In research questions Q2 - Q4 two-way ANOVAs were used to test the effects of gender and subject. Results indicate equal shares of female and male students among the top performers, with women overrepresented in the humanities and men overrepresented in STEM relative to their proportion of the student population. The analysis of socio-emotional and learning-related factors showed risk factors for high performing female students such as lower self-efficacy, but no major emotional vulnerability. Overall, the data suggest that at the beginning of the COVID-19 pandemic, female top performers had still been able to compensate for the risk factors.<br
Keywords: Gender; STEM; Humanities; Higher Education; High Ability; COVID-19; Digital Learning; Socio-emotional perceptions

First steps toward assessing talent-support systems on a country level - Ziegler, Albert; Stoeger, Heidrun (High ability studies, 2023)
A growing number of countries has a strong interest in assessing the quality of their talent-support systems. We propose combining two relevant conceptual frameworks - hemerotopes and the learning and educational capital approach - to better achieve this end. Hemerotopes provide qualitative categories for assessing the degree to which countries have transformed environments to support talent development. We postulate six different hemerotopes, distinguished by two dimensions: the degree of support for talent development and the outcomes of the talent development process. The six hemerotopes range from atopes (no support of talent development and no outcomes of talent development) to megatopes (very high support of talent development and outstanding outcomes of talent development). Thus, among the different types of hemerotopes, the number of megatopes plays an especially important role when it comes to assessing the quality of a country's talent-support system. The learning capital approach, then, facilitates the comparative analysis of the quality of hemerotopes. In this approach, endogenous and exogenous learning resources are distinguished, making it possible to analyze simultaneously the learning resources available in a hemerotope as well as individuals' capacities to use these environmental resources.
CRIS-Team WoS Importer:2023-05-19

Forschung - Ziegler, Albert (Bildungspsychologie, 2010)

Forschungsperspektiven der Begabungsforschung: Der Tower of Creativity - Ziegler, Albert; Harder, Bettina; Trottler, Susanne (Journal für Begabtenförderung, 2011)

Für das Leben lernen: Von der traditionellen Lernstoffvermittlung zum selbsregulierten Lernen - Ziegler, Albert (Oberbayerische Schulzeitung, 2009)

Ganzheitliche Förderung: Die Rolle von Bildungs- und Lernkapital - Vladut, Anamaria; Ziegler, Albert (Schulmagazin 5 - 10 : Impulse für kreativen Unterricht, 2013)

"Ganzheitliche Förderung" umfasst mehr als nur die Person: Aktiotop- und Soziotopförderung - Ziegler, Albert (Heilpädagogik online, 2009)

Gender differences in mathematics and science: The role of the actiotope in determining individuals' achievements and confidence in their own abilities - Ziegler, Albert; Stöger, Heidrun; Harder, Bettina; Park, K; Portesová, S; Porath, Marion (High ability studies, 2014)

“Generation invisible?“. Higher education students’ (non)use of webcams in synchronous online learning - Bedenlier, Svenja; Wunder, Iris; Gläser-Zikuda, Michaela; Kammerl, Rudolf; Kopp, Bärbel; Ziegler, Albert; Händel, Marion (International Journal of Educational Research Open, 2021)
The pandemic situation continues to influence teaching and learning in higher education, with students oftentimes participating in synchronous videoconferencing sessions as a means to interact with peers and instructors. The frequently noted non-use of webcams by students incited the current study, investigating usage behavior as well as potentially related course variables and individual characteristics. N = 3,527 students from a German university took part in an online survey at the end of the regular summer term 2020 (August 2020). Findings indicate that students’ webcam usage behavior was related to personal thoughts and feelings (e.g., privacy), to course characteristics (e.g., group cohesion), and it differed due to specific groups (gender, study level). With the ongoing importance of videoconferencing in higher education, this study provides a foundation for further investigation into this synchronous learning context. <
Keywords: Webcam use; COVID-19 pandemic; Social presence; Individual differences

Geschlechterunterschiede in MINT: Empirische Befunde, Erklärungsansätze und Interventionsmöglichkeiten - Stöger, Heidrun; Ziegler, Albert; Heilemann, M (LIT, 2012)
UnivIS-Import:2015-04-02:Pub.2012.phil.dps.ipsy1.lpsych_2.geschl

Geschlechterunterschiede in MINT: Empirische Befunde, Erklärungsansätze und Interventionsmöglichkeiten - Stöger, Heidrun; Ziegler, Albert; Heilemann, M (LIT, 2012)
UnivIS-Import:2015-05-08:Pub.2012.phil.dps.ipsy1.lpsych_2.soziot

Gifted education as a lifelong challenge. Essays in honor of Franz J. Moenks (PSYNDEXalert) - Ziegler, Albert; Fischer, C; Stöger, Heidrun; Reutlinger, Marold (Lit, 2012)

Gifted education as a lifelong challenge : essays in honour of Franz J. Mönks - Ziegler, Albert; Fischer, Christian; Stöger, Heidrun; Reutlinger, Marold (Lit, 2012)

Gifted education in Arab countries: analyses from a learning-resource perspective - Ismail, Sadiq A. A.; Alghawi, Mariam Ali; Alsuwaidi, Khalifa A.; Ziegler, Albert (Cogent Education, 2022)
CRIS-Team WoS Importer:2022-09-16

Gifted education in German-speaking Europe - Ziegler, Albert; Stöger, Heidrun; Harder, Bettina; Balestrini, Daniel Patrick (Journal for the education of the gifted, 2013)

Gifted education in modern Asia: Analyses from a systemic perspective - Vialle, W; Ziegler, Albert (Gifted Education in Asia: Problems and Prospects, 2015)

Gifted Identification Kit 4 - 6 for the United Arab Emirates - Ziegler, Albert; Stöger, Heidrun (UAE: HADAP, 2016)

Giftedness and gifted education: The need for a paradigm change - Ziegler, Albert; Stöger, Heidrun; Vialle, W (Gifted child quarterly, 2012)

Giftedness and talent research in the People ́s Republic of China: Aims and objectives - Liu, Q; Sudzina, P H; Ziegler, Albert (Talent Talks, 2012)

Giftedness research in the 21st century - Ziegler, Albert (International handbook on giftedness, 2009)

Göçmen kökenlı üstün zekali çocuklar: Göçmen kökenlı aılelere, öğretmenlere ve eğıtımcılere yönelık bılgılendırme - Reutlinger, Marold; Leana-Tasçilar, MarilenaZ.; Ziegler, Albert (2015)

Helplessness among University Students: An Empirical Study Based on a Modified Framework of Implicit Personality Theories - Ziegler, Albert; Bedenlier, Svenja; Gläser-Zikuda, Michaela; Kopp, Bärbel; Händel, Marion (Education Sciences, 2021)
Due to the COVID-19 pandemic, and within a very short period of time, teaching in the 2020 summer term changed from predominantly on-site to online instruction. Students suddenly faced having to adapt their learning process to new demands for which they may have had both insufficient digital skills and a lack of learning resources. Such a situation carries the risk that a substantial number of students become helpless. The aim of our empirical study was to test a hybrid framework of helplessness that includes both objective causes of helplessness and students’ subjective interpretations of them. Before lectures or courses began, students of a full-scale university were invited to participate in an online survey. The final sample consists of 1690 students. Results indicate that objective factors as well as their subjective interpretations contributed to the formation of helplessnes
CRIS-Team Scopus Importer:2021-11-05
Keywords: higher education; digital learning; COVID-19 pandemic; helplessness; implicit theories of personality

Helplessness Among University Students: An Empirical Study Based on a Modified Framework of Implicit Personality Theories - Ziegler, Albert; Gläser-Zikuda, Michaela; Kopp, Bärbel; Bedenlier, Svenja; Händel, Marion (Journal of Science Education, 2021)
Due to the COVID-19 pandemic, and within a very short period of time, teaching in the 2020 summer term changed from predominantly on-site to online instruction. Students suddenly faced having to adapt their learning process to new demands for which they may have had both insufficient digital skills and a lack of learning resources. Such a situation carries the risk that a substantial number of students become helpless. The aim of our empirical study was to test a hybrid framework of helplessness that includes both objective causes of helplessness and students' subjective interpretations of them. Before lectures or courses began, students of a full-scale university were invited to participate in an online survey. The final sample consists of 1,690 students. Results indicate that objective factors as well as their subjective interpretations contribute to the formation of helplessnes

Heterogenität und Inklusion im Unterricht - Stöger, Heidrun; Ziegler, Albert (Schulpädagogik heute, 2013)

Heterogenität und Inklusion im Unterricht - Ziegler, Albert; Stöger, Heidrun (Studienbuch Schulpädagogik, 2012)
UnivIS-Import:2015-04-20:Pub.2012.phil.dps.ipsy1.lpsych_2.hetero

Hochbegabtenförderung - Ziegler, Albert; Grassinger, Robert; Mader, Bettina (LVH aktuell, 2009)

Hochbegabte und Begabtenförderung - Ziegler, Albert (Handbuch Bildungsforschung, 2010)

Hochbegabung (Themenheft) - Stöger, Heidrun; Ziegler, Albert (Heilpädagogik online, 2009)
UnivIS-Import:2015-03-09:Pub.2009.phil.dps.ipsy1.lpsych_2.hochbe

Hochbegabung und Migrationshintergrund: Informationen für Eltern und Pädagogen von Kindern mit Migrationshintergrund - Reutlinger, Marold; Leana-Tasçilar, MarilenaZ.; Ziegler, Albert (2015)

How Desirable Are Gifted Boys for Girls, and Gifted Girls for Boys? Results of a Chatroom Study - Ziegler, Albert; Fidelman, Marina; Reutlinger, Marold; Neubauer, Tanja; Heilemann, M (Australasian journal of gifted education, 2011)

How fine motor skills influence the assessment of high ability and unterachievement - Ziegler, Albert; Stöger, Heidrun (Journal for the education of the gifted, 2010)
UnivIS-Import:2015-03-09:Pub.2010.phil.dps.ipsy1.lpsych_2.howfin

How intelligent, popular and nice are high achieving students according to the perceptions of their school teachers? Results of a cross-cultural study with teachers from eight countries - Leana-Tasçilar, MarilenaZ.; Blumen, S; Eberle, Thomas; Escobedo, P. S.; Jurisevic, M; Li, X.; Roy, P.; Sak, U.; Shi, J; Vialle, W; Ziegler, Albert (Talents in Motion, 2016)

How Mentors Think About the Attainability of Mentoring Goals: The Impact of Mentoring Type and Mentoring Context on the Anticipated Regulatory Network and Regulatory Resources of Potential Mentors for School Mentoring Programs - Mader, Matthias; Stoeger, Heidrun; Veas, Alejandro; Ziegler, Albert (Frontiers in Psychology, 2021)
Research shows that trained mentors achieve better results than untrained ones. Their training should particularly address their expectations for their future mentoring. Our study involved 190 preservice teachers, potential mentors of ongoing school mentoring for primary and secondary school students of all grades. They were randomly assigned to one of four conditions in a 2-x-2 between-subjects design of mentoring type (traditional mentoring versus e-mentoring) and mentoring context (non-pandemic versus COVID-19 pandemic). Participants assessed mentoring conducted under these four conditions in terms of its appropriateness for achieving four mentoring program targets: learning, key skills, social targets, and problem coping. Participants were also asked to assess the resources available to achieve each program target. Overall, the potential mentors considered the various conditions to be suitable for achieving the four program targets. They were particularly favorable in their assessment of the possibility for the realization of learning targets. Likewise, they assumed that sufficient resources were available to achieve the targets. However, a repeated-measures MANOVA showed that the potential mentors considered more ambitious targets to be possible in traditional mentoring than in e-mentoring and normal (i.e., pre-pandemic) contextual conditions than during the COVID-19 pandemic. In contrast, they estimated the resources available to achieve the targets to be about the same in the four conditions. This indicates a decoupling of mentoring targets from the consideration of the resources needed to achieve them. This assumption was confirmed in correlation analyses and has implications for mentor training.
CRIS-Team Scopus Importer:2021-12-03
Keywords: COVID-19; e-mentoring; mentor expectation; mentor training; mentoring; mentoring goal; mentors; school mentoring

Identification of underachievement: an empirical study on the agreement among various diagnostic sources - Ziegler, Albert; Stöger, Heidrun (Gifted and talented education : major themes in education, 2009)

Identifying effective learning environments. Part 1 [Special issue] - Schorer, J; Baker, Joseph; Stöger, Heidrun; Ziegler, Albert (Psychological Test and Assessment Modeling, 2015)

Identifying effective learning environments. Part 2 - Stöger, Heidrun; Baker, Joseph; Schorer, J; Ziegler, Albert (Psychological Test and Assessment Modeling, 2015)

Identifying the causes of underachievement: A plea for the inclusion of fine motor skills - Stöger, Heidrun; Suggate, S; Ziegler, Albert (Psychological Test and Assessment Modeling, 2013)

Impact of a teacher-led intervention on preference for self-regulated learning finding main ideas in expository texts and reading comprehension - Stöger, Heidrun; Sontag, Christine; Ziegler, Albert (Journal of Educational Psychology, 2014)
We examined the impact of a teacher-led intervention, implemented during regular classroom instruction and homework, on fourth-grade students' preference for self-regulated learning, finding main ideas in expository texts, and reading comprehension. In our quasi-experimental study with intact classrooms, (a) students (n = 266, 12 classrooms) who received regular classroom instruction (REG) were compared with (b) students (n = 268, 12 classrooms) who were taught text reduction strategies (TEXT) and © students (n = 229, 9 classrooms) who were introduced to text reduction strategies within the framework of a 7-step cyclical model of self-regulated learning (SRL + TEXT). Participating classrooms were semi-randomly assigned to 1 of the 3 conditions, with the restriction that teachers from one school could not be in different intervention conditions. Both in their posttest and follow-up test results (11 weeks after the intervention), SRL + TEXT students showed a stronger preference for self-regulated learning than students of the 2 other groups. The SRL + TEXT students also identified more main ideas over the course of the intervention. Positive effects on reading comprehension in a standardized test were restricted to students without migration background. (PsycINFO Database Record © 2014 APA, all rights reserved).
UnivIS-Import:2015-03-09:Pub.2014.phil.dps.ipsy1.lpsych_2.impact

Implicit personality theories on the modifiability and stability of the action repertoire as a meaningful framework for individual motivation: A cross-cultural study - Ziegler, Albert; Fidelman, Marina; Reutlinger, Marold; Vialle, W; Stöger, Heidrun (High ability studies, 2010)

Inclusive gifted education: If not now, when? - Nunez, Miguelina; Gläser-Zikuda, Michaela; Ziegler, Albert (2020)

Inclusive gifted education: Voices from around the world - Nunez, Miguelina; Gläser-Zikuda, Michaela; Ziegler, Albert (2020)

India in World Science - Porath, Marion; Ziegler, Albert (Talent Talks, 2010)

Individuelle Begabungsförderung in Lernsoziotopen - Ziegler, Albert (Individuelle Förderung multipler Begabungen, 2010)
UnivIS-Import:2015-04-20:Pub.2010.phil.dps.ipsy1.lpsych_2.indivi

Individuelle Zielorientierung und wahrgenommene Klassenzielstruktur im Grundschulalter - Finsterwald, Monika; Ziegler, Albert; Dresel, Markus (Zeitschrift für Entwicklungspsychologie und Pädagogische Psychologie, 2009)

Integrated STEM for regular and gifted students in Germany - Händel, Marion; Ziegler, Albert (Promoting the gifted to be real-world problem-solvers through interdisciplinary education, 2012)

International perspectives and trends in research on giftedness and talent development - Stöger, Heidrun; Balestrini, Daniel Patrick; Ziegler, Albert (APA Handbook on giftedness and talent, 2016)

Kapitale in der Musik - Straßer, Sabrina; Groß, Carolin; Pfeiffer, Wolfgang; Ziegler, Albert (Journal für Begabtenförderung, 2013)

Key issues in professionalizing mentoring practices - Stoeger, Heidrun; Balestrini, Daniel Patrick; Ziegler, Albert (Annals of the New York Academy of Sciences, 2020)
Mentoring has experienced a tremendous upswing over the past decades, which has only recently slowed down somewhat. One possible factor explaining mentoring's popularity are numerous case studies suggesting that it is one of the most effective ways of helping individuals to develop. Meta-analyses indicating effect sizes for mentoring that are below what would theoretically be possible appear to contradict the success stories, however. This circumstance raises questions about the professionalization of mentoring practices. We focus on seven key issues for future efforts at professionalizing mentoring. Key issues 1 and 2 address observation of the state of the art within formal mentoring when programs are planned and implemented: the consideration of recent research and of best practices. While both areas can overlap, they provide complementary sources of pertinent information for the professionalization of mentoring. Key issues 3-6 address the need to align mentoring activities to the specific context and goals of individual mentoring programs by observing idiographic program characteristics, mentoring dynamics, the orchestration of mentoring goals, and the provision of mentoring resources. Finally, key issue 7 highlights ongoing evaluation as the basis of the effective, continuous improvement of mentoring programs.
CRIS-Team WoS Importer:2020-12-18

Kompetenzen zum selbstregulierten Lernen im Studium: Ergebnisse der Befragung von Expert(inn)en aus vier Studienbereichen - Steuer, G; Engelschalk, Tobias; Jöstl, Gregor; Roth, A; Wimmer, Bastian; Schmitz, Björn; Schober, B; Spiel, Christiane; Ziegler, Albert; Dresel, M. (Zeitschrift für Pädagogik, 2015)

Konzepte der Hochbegabtenberatung in der Praxis - Ziegler, Albert; Grassinger, Robert; Harder, Bettina (LIT, 2012)
UnivIS-Import:2015-04-02:Pub.2012.phil.dps.ipsy1.lpsych_2.konzep_5

Konzepte der Hochbegabtenberatung in der Praxis - Ziegler, Albert; Grassinger, Robert; Harder, Bettina (Lit, 2012)

Konzepte der Hochbegabungsberatung in der Praxis - Ziegler, Albert; Grassinger, Robert; Harder, Bettina (LIT, 2012)
UnivIS-Import:2017-07-10:Pub.2012.phil.dps.ipsy1.lpsych_2.dasber

Learning how to learn through homework. A six-week training program for children in the middle primary years with sample mathematics content - Ziegler, Albert; Stöger, Heidrun; Vialle, W (Hawker Brownlow, 2013)

Learning resources and talent development from a systemic point of view - Ziegler, Albert; Debatin, Tobias; Stoeger, Heidrun (Annals of the New York Academy of Sciences, 2019)
System theories postulate that a system needs resources in order to evolve and function as an entirety. According to the actiotope model of giftedness, exogenous and endogenous resources needed to develop excellence include five forms of educational capital (economic, cultural, social, infrastructural, and didactic) and five forms of learning capital (organismic, telic, actional, episodic, and attentional), independent of domain and level of talent development. In three studies, we addressed several blind spots in the empirical basis of the educational and learning capital (ELC) approach. The studies were conducted in different domains, with different samples, and on various levels of talent development, as well as with regard to different functions for which resources can be used. Study 1, comprising 365 sixth graders, showed that ELC have an incremental validity beyond IQ for predicting scholastic achievement. In study 2 with 90 women holding a university degree in science, technology, engineering, and mathematics (STEM), we provide evidence that in the collegiate actiotopes of women who were later successful in STEM, more ELC had been available and was used to serve different functions than in the actiotopes of less successful women in STEM. In study 3 with 74 long-distance runners, we found a similar pattern of results for different achievement levels in an athletics domain.
CRIS-Team Scopus Importer:2019-06-18
Keywords: actiotope; educational capital; learning capital; learning resources; talent development

Learning resources within the Actiotope: A validation study of the QELC (Questionnaire of Educational and Learning Capital) - Vladut, Anamaria; Vialle, W; Ziegler, Albert (Psychological Test and Assessment Modeling, 2015)

Little Einstein in my classroom: results of a cross-cultural study with teachers - Jurisevic, M; Blumen, S; Eberle, Thomas; Sánchez-Escobedo, P; Park, K; Roy, P; Sak, U; Li, X; Shi, S; Leana-Tasçilar, MarilenaZ.; Vialle, W; Ziegler, Albert (Educational change: Challenges and expectations, 2016)

Mädchen und Frauen in MINT : Bedingungen von Geschlechtsunterschieden und Interventionsmöglichkeiten - Stöger, Heidrun; Ziegler, Albert; Heilemann, M (Lit, 2012)

Mathematical foundations of and empirical investigations into the dynamic of top positions: Stabilization effect, reserved Matthew Effect, and Heraclitus Effect - Ziegler, A Jr; Heckel, A; Ziegler, Albert (Psychological Test and Assessment Modeling, 2013)

Mediation analysis of the relationship between educational capital, learning capital and underachievement among gifted secondary school students - Veas, A; Castejón, J-L; O´Reilly, C; Ziegler, Albert (Journal for the education of the gifted, 2016)

Mentoring: A review - Grassinger, Robert; Porath, Marion; Ziegler, Albert (High ability studies, 2010)
UnivIS-Import:2015-03-09:Pub.2010.phil.dps.ipsy1.lpsych_2.mentor

Mentoring entlang eines Lernpfades: Eine Mixed-Methods Studie - Daunicht, Tina-Myrica; Emmerdinger, Kathrin J.; Stoeger, Heidrun; Ziegler, Albert (Sektionstagung der Arbeitsgruppe für empirische pädagogische Forschung (AEPF), 2022)

Mentoring entlang eines Lernpfades: Gelingensbedingungen für ein schulbasiertes 1:1-Mentoring-Programm - Daunicht, Tina-Myrica; Matthes, Benjamin; Quarda-Häußler, Ann-Kathrin; Emmerdinger, Kathrin J; Stoeger, Heidrun; Ziegler, Albert (5. LemaS-Jahrestagung, 2022)

Mentoring: Königsweg der Pädagogik oder überschätzte Fördermaßnahme? - Ziegler, Albert; Stöger, Heidrun (Diskurs Kindheits- und Jugendforschung, 2012)
UnivIS-Import:2015-03-09:Pub.2012.phil.dps.ipsy1.lpsych_2.mentor

Mentoring: Konzeptuelle Grundlagen und Wirksamkeitsanalyse - Ziegler, Albert (Mentoring : Theoretische Hintergründe, empirische Befunde und praktische Anwendungen, 2009)

Mentorings bedürfen einer professionellen Durchführung - Eine empirische Untersuchung der Risikofaktoren von Mentorings - Buschhaus, F; Schirner, Sigrun; Stöger, Heidrun; Ziegler, Albert (Journal für Begabtenförderung, 2013)

Mentoring the gifted: a conceptual analysis - Ziegler, Albert; Grassinger, Robert; Porath, Marion (High ability studies, 2010)

Mentoring: Theoretische Hintergründe, empirische Befunde und praktische Anwendungen - Stöger, Heidrun; Ziegler, Albert; Schimke, Diana (Pabst, 2009)
UnivIS-Import:2015-04-02:Pub.2009.phil.dps.ipsy1.lpsych_2.mentor

Mentoring : Theoretische Hintergründe, empirische Befunde und praktische Anwendungen - Stöger, Heidrun; Ziegler, Albert; Schimke, Diana (Pabst, 2009)

Mentoring: Theoretischer Hintergrund - Ziegler, Albert (Mentoring: Theoretische Hintergründe, empirische Befunde und praktische Anwendungen, 2009)
UnivIS-Import:2015-04-20:Pub.2009.phil.dps.ipsy1.lpsych_2.mentor_0

MINT-Talentförderung im nationalen und internationalen Kontext - Ziegler, Albert; Heller, K A; Mönks, F J (Journal für Begabtenförderung, 2011)

Modeling social, dimensional, and temporal comparisons in self-concept development with the random intercept cross-lagged panel model: A methodological-substantive integration - Debatin, Tobias; Stoeger, Heidrun; Ziegler, Albert (Developmental Psychology, 2023)
In recent years, discussion of the limitations of the standard cross-lagged panel model (CLPM) has increased, and the random intercept cross-lagged panel model (RI-CLPM) has been proposed as an improved approach to modeling. By now, there are some first applications of the model to investigate reciprocal relations in self-concept development. However, a methodological-substantive integration of the model in the context of the three major comparison processes in self-concept development is still missing, and it has not been used to evaluate dimensional and temporal comparison effects. We provide such an integration in self-concept theory and applied the RI-CLPM to investigate social, dimensional, and temporal comparison effects simultaneously. Investigating a sample of 701 German students from the middle of Grade 9 to the middle of Grade 10, we confirmed previous results by finding trait-like stability in science, technology, engineering, and mathematics (STEM) self-concept as well as in STEM and language achievement. We also found evidence for all three comparison effects, but evidence for dimensional comparison effects was only found at the between-person level of the RI-CLPM. (PsycInfo Database Record (c) 2023 APA, all rights reserved).
CRIS-Team Scopus Importer:2023-09-01

Modelling, assessing, and promoting competences for self-regulated learning in higher education - Eckerlein, N.; Dresel, M.; Steuer, G.; Foerst, N.; Ziegler, Albert; Schmitz, B.; Spiel, C.; Schober, B. (Student Learning in German Higher Education: Innovative Measurement Approaches and Research Results, 2020)
Summarized are the results of a research project that focused on assessing and fostering competences for self-regulated learning in higher education. Innovative instruments (situational judgement test, competence-performance-assessment, learning journal) to assess different aspects of self-regulated learning (e.g., use of cognitive and metacognitive strategies, strategies of motivational regulation) were developed and validated. Moreover, training approaches to foster different aspects of self-regulated learning strategy use were conceptualized, also to test the change sensitivity of the assessments. In detail, the importance of competences for self-regulated learning for central componentsof successful learning processes and study success (e.g., invested effort, exam grades, subjective well-being, procrastination) are outlined.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Assessment; Competence modelling; Generic competences; Self-regulated learning; Strategy use; Training

Models of giftedness put to the empirical test - Harder, Bettina; Vialle, Wilma; Ziegler, Albert (High ability studies, 2014)

Motivational Orientations of High-Achieving Students as Mediators of a Positive Perception of a High-Achieving Classmate: Results from a Cross-national Study - Oh, Hyerim; del Mar Badia, M; Blumen, S; Maakrun, J; Nguyen, Quoc Anh-Thu; Stack, N; Sutherland, Margaret; Wormald, C; Ziegler, Albert (Anales de Psicología, 2016)

Neue empirische Befunde zum Underachievement Hochbegabter - Martzog, Philipp; Stöger, Heidrun; Ziegler, Albert (Heilpädagogik online, 2009)

New approaches to the study of self-regulated learning - Porath, Marion; Stöger, Heidrun; Ziegler, Albert (Psychological Test and Assessment Modeling, 2010)
UnivIS-Import:2015-03-09:Pub.2010.phil.dps.ipsy1.lpsych_2.newapp

Nine years of online mentoring for secondary school girls in STEM: an empirical comparison of three mentoring formats - Stoeger, Heidrun; Heilemann, Michael; Debatin, Tobias; Hopp, Manuel; Schirner, Sigrun; Ziegler, Albert (Annals of the New York Academy of Sciences, 2020)
Online mentoring can be useful for supporting girls in science, technology, engineering, and mathematics (STEM). Yet, little is known about the differential effects of various online mentoring formats. We examine the general and relative effectiveness of three online mentoring formats, one-on-one mentoring, many-to-many group mentoring, and a hybrid form of the two. All three formats were implemented in different years in the Germany-wide online-only mentoring program, CyberMentor, whose platform enables communication and networking between up to 800 girls (in grades 5-13) and 800 women (STEM professionals) each year. We combined longitudinal mentee data for all first-year participants (N = 4017 girls,M-age = 14.15 years) from 9 consecutive mentoring years to evaluate and compare the three mentoring formats. Overall, all formats effected comparable increases in mentees' STEM activities and certainty about career plans. However, mentees' communication behavior and networking behavior on the mentoring platform differed between the three formats. Mentees in the hybrid mentoring format showed the most extensive STEM-related communication and networking on the platform. We also analyzed the explanatory contributions of STEM-related communication and networking on interindividual differences in the developmental trajectories of mentees' STEM activities, elective intentions in STEM, and certainty about career plans, for each format separately.
CRIS-Team WoS Importer:2020-09-18

Not only a question of Etiquette: Pitfalls in addressing the gifted. Considerations and analyses based on a modified Dweck framework - Ziegler, Albert; Stöger, Heidrun (Learning and individual differences, 2010)

Online mentoring as an extracurricular measure to encourage talented girls in STEM (Science, Technology, Engineering, and Mathematics): An empirical study of one-on-one versus group mentoring - Stöger, Heidrun; Hopp, Manuel; Ziegler, Albert (Gifted child quarterly, 2017)

Online mentoring for girls in secondary education to increase participation rates of women in STEM: A long-term follow-up study on later university major and career choices - Stoeger, Heidrun; Debatin, Tobias; Heilemann, Michael; Schirner, Sigrun; Ziegler, Albert (Annals of the New York Academy of Sciences, 2023)
An important first step in talent development in science, technology, engineering, and mathematics (STEM) is getting individuals excited about STEM. Females, in particular, are underrepresented in many STEM fields. Since girls' interest in STEM declines in adolescence, interventions should begin in secondary education at the latest. One appropriate intervention is (online) mentoring. Although its short-term effectiveness has been demonstrated for proximal outcomes during secondary education (e.g., positive changes in elective intentions in STEM), studies of the long-term effectiveness of STEM mentoring provided during secondary education-especially for real-life choices of university STEM majors and professions-are lacking. In our study, we examine females' real-life decisions about university majors and entering professions made years after they had participated in an online mentoring program (CyberMentor) during secondary education. The program's proximal positive influence on girls' elective intentions in STEM and certainty about career plans during secondary education had previously been demonstrated in several studies with pre-post-test waitlist control group designs. Specifically, we compared the choices that former mentees (n = 410) made about university majors and entering professions several years after program participation with (1) females of their age cohort and (2) females of a group of girls comparably interested in STEM who had signed up for the program but then not participated (n = 71). Further, we examined the explanatory contribution to these later career-path-relevant, real-life choices based on (1) mentees' baseline conditions prior to entering the program (e.g., elective intentions in STEM), (2) successful 1-year program participation, and (3) multiyear program participation. Findings indicate positive long-term effects of the program in all areas investigated.
CRIS-Team WoS Importer:2023-04-28

Online Mentoring for Talented Girls in STEM: The Role of Relationship Quality and Changes in Learning Environments in Explaining Mentoring Success - Stoeger, Heidrun; Debatin, Tobias; Heilemann, Michael; Ziegler, Albert (New directions for child and adolescent development, 2019)
Although participation rates of women in science, technology, engineering, and mathematics (STEM) are continually improving, low rates are still an issue in many countries. While previous studies found positive effects of online mentoring for increasing girls' interests in STEM, research concerning explanatory mechanisms is lacking. We found evidence that in a 1-year online mentoring program for girls (age: M = 13.82 years, N = 998) in STEM, suitably implemented mentoring (operationalized via relationship quality in a program that systematically incorporates structural and organizational aspects of successful mentoring) was associated with positive changes in the learning environments of the mentees (as indicated by their increasing educational capital). These positive changes were associated with increases in the program-related mentoring outcomes STEM activities and elective intentions in STEM. Finally, we found that suitably implemented online mentoring was indirectly related to an increase in these two mentoring outcomes via an increase in educational capital. These results indicate the importance of paying close attention to learning environments when planning interventions. (c) 2019 The Authors. New Directions for Child and Adolescent Development published by Wiley Periodicals, Inc.
CRIS-Team WoS Importer:2021-10-18

Pädagogik und Bildungsökonomie - Ziegler, Albert (LVH aktuell, 2010)

Pädagogik und Bildungsökonomie - Ziegler, Albert (SwissGifted, 2010)

Parental goal orientations for their kindergarten children: Introductiong the Nuremberg Parental Goal Oriantiation Scales (NuPaGOS) - Reutlinger, Marold; Ballmann, Anke; Vialle, W; Zhang, Zhitian; Ziegler, Albert (Psychological Test and Assessment Modeling, 2015)

Parental Stress Provoked by Short-Term School Closures During the Second COVID-19 Lockdown - May, Isabelle; Awad, Sarah; May, Matthias; Ziegler, Albert (Journal of Family Issues, 2021)
Governments of numerous countries implemented school closures to contain the COVID-19 pandemic. Several investigations have shown the negative impact of social-distancing policies and school closures on children worldwide. Recently, research also demonstrated adverse effects on adults’ well-being. The development of children is strongly affected by their parent’s emotional state. The present study aimed to examine parental stress levels caused by a short period of homeschooling in December 2020 in Germany. A structured survey was set up and distributed randomly via social media and parent associations. We observed a significant increase in stress and concerns. Family conflicts significantly increased, social isolation was feared, and powerlessness and helplessness ascended. Risk factors were parental education levels, parental working time, and teaching features like the frequency of feedback, correction, and accessibility.
CRIS-Team Scopus Importer:2021-10-22
Keywords: childhood; COVID-19; exposed children; family relations; parental stress

Prädiktoren einer langfristigen Teilnahme an einem E-Mentoring-Programm - Schimke, Diana; Stöger, Heidrun; Ziegler, Albert (Mentoring : Theoretische Hintergründe, empirische Befunde und praktische Anwendungen, 2009)

Praise in gifted education: analyses on the basis of the actiotope model of giftedness - Stöger, Heidrun; Ziegler, Albert (Gifted and talented education, 2009)

Preservice Teachers' Online Self-Regulated Learning: Does Digital Readiness Matter? - Fuchs, Katharina; Pösse, Lisa; Bedenlier, Svenja; Gläser-Zikuda, Michaela; Kammerl, Rudolf; Kopp, Bärbel; Ziegler, Albert; Händel, Marion (Education Sciences, 2022)
(1) Background: Teaching in today's schools asks teachers to foster self-regulated learning and digital competences in children and young people. In order to do so, teachers first need to acquire and use these competences themselves. (2) Methods: Based on a mixed-methods approach, the study investigates self-regulated learning in online courses of N = 129 preservice teachers at a German university. (3) Results and conclusions: Perceiving their digital readiness as generally high, preservice teachers appear to not overly self-regulate their learning in the online environment. Finally, preservice teachers' digital readiness was related only weakly to their online self-regulated learning. A discussion is offered which shows teacher education as a broader phenomenon and implies the need for professional development for teacher educators. Additionally, it is argued to link research on self-regulated learning more closely to research on online learning environments in teacher education.
CRIS-Team WoS Importer:2022-05-06

Quantitative approaches to the study of self-regulated learning - Ziegler, Albert; Stöger, Heidrun; Porath, Marion (Psychological Test and Assessment Modeling, 2011)
UnivIS-Import:2015-03-09:Pub.2012.phil.dps.ipsy1.lpsych_2.quanti

Quantitative text analysis in gifted and talented research - Balestrini, Daniel Patrick; Stoeger, Heidrun; Ziegler, Albert (High ability studies, 2023)
The authors introduce readers to quantitative text analysis and its potential for analyzing text-based nonreactive measures as a means of broadening the evidential basis within research on giftedness and talent. After defining quantitative text analysis and describing how it can augment survey studies for analyses at individual and cultural levels, the special potential of quantitative text analysis for addressing cultural questions within gifted and talented research is described. Inductive and deductive techniques of quantitative text analysis are then introduced and illustrated with brief examples drawn from gifted and talented research. Finally, a brief illustrative study is presented via an extended series of linked worked examples focusing on the question of the place of giftedness and talent within mentoring discourse in US mass media of past and present in order to illustrate in more detail how quantitative text analysis can be used to improve the culture-level evidence base within gifted and talented education.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Gifted and talented; gifted education; mentoring; nonreactive measures; quantitative text analysis; talent development

Recent trends in the study of giftedness - Oarga, C; Harder, Bettina; Stöger, Heidrun; Ziegler, Albert (Talent Talks, 2010)

Research on a modified framework of implicit personality theories - Ziegler, Albert; Stöger, Heidrun (Learning and individual differences, 2010)

Resource-oriented Counseling at the State-Wide Counseling and Research Center for the Gifted at the University of Erlangen-Nuremberg - Trottler, Susanne; Harder, Bettina; Ziegler, Albert (3rd International Conference on Talent Development & Excellence, 2013)

Ressourcenorientierte Begabungsberatung - Trottler, Susanne; Harder, Bettina; Ziegler, Albert (21. Jahrestagung der Kommission Grundschulforschung und Pädagogik der Primarstufe der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2012)

Ressourcenorientierte Begabungsberatung - Trottler, Susanne; Harder, Bettina; Ziegler, Albert (Individuelle Förderung und Lernen in der Gemeinschaft. Jahrbuch Grundschulforschung, 2013)
UnivIS-Import:2015-04-20:Pub.2013.phil.dps.ipsy1.lpsych_2.ressou

Selbstreguliertes Lernen Hochbegabter - Ziegler, Albert (Begabtenförderung und Schulsystem, 2009)
UnivIS-Import:2015-04-20:Pub.2009.phil.dps.ipsy1.lpsych_2.selbst_0

Selbstreguliertes Lernen in der Grundschule - Stöger, Heidrun; Sontag, Christine; Ziegler, Albert (Lernstrategien im Grundschulalter : Konzepte, Befunde und praktische Implikationen, 2009)

Self-Regulated Resource Management in Emergency Remote Higher Education – Status Quo and Predictors - Naujoks, Nick; Bedenlier, Svenja; Gläser-Zikuda, Michaela; Kammerl, Rudolf Josef; Kopp, Bärbel; Ziegler, Albert; Händel, Marion (Frontiers in Psychology, 2021)
Because of the COVID-19 pandemic in the spring term 2020, students faced a sudden change from on-campus learning to online learning with synchronous and asynchronous online courses (emergency remote teaching). To study successfully, students not only needed to be prepared in terms of digital readiness (workspace, IT equipment, previous online learning experiences, and sharing information online), they also faced challenges that pertained to the self-regulated management of external resources (environment structuring, time management, and help-seeking). In the current study, we investigated students’ digital readiness for the sudden switch to online learning; differences between students’ intended and actual use of external resource management strategies; and the influence of students’ digital readiness on their actual use of resource management strategies. Students enrolled in a full-scale, German university (N = 662) answered two online questionnaires (before and in the middle of the term). Descriptive statistics indicated that students seemed to be ready to study online. However, a repeated measures analysis of variance showed that students were not able to manage their resources during the term as frequently as intended. Finally, separate regression analyses revealed that availability of workspace and IT equipment predicted the use of environment structuring strategies. Additionally, IT equipment and information sharing behavior predicted students’ help-seeking. Based on the current results, we discuss implications for the promotion of student self-regulated learning in online emergency remote teaching based on both external resources and digital readiness.

Self-regulatory training through elementary students' homework completion - Ziegler, Albert; Stöger, Heidrun (Handbook of self-regulation of learning and performance, 2011)

Shortcomings of the IQ-Based Construct of Underachievement - Ziegler, Albert; Stöger, Heidrun (Roeper review, 2012)

Soaring up the Tower of Creativity - Ziegler, Albert; Vialle, W (Creativity in business and education: Interdisciplinary and cultural aspects, 2010)

Social Environmental Factors and Personal Motivational Factors Associated with Creative Achievement: A Cross-Cultural Perspective - Zhang, Zhitian; Hoxha, Linda; Aljughaiman, Abdullah; Arenliu, Aliriza; Gomez-Arizaga, Maria P.; Gucyeter, Sule; Ponomareva, Irina; Shi, Jiannong; Irueste, Paula; Rogl, Silke; Nunez, Miguelina; Ziegler, Albert (Journal of Creative Behavior, 2020)
Although the theory of the socio-cultural approach to creativity is gaining steam, empirical studies with advanced statistical tools are lagging behind. To address the gap of empirical studies integrating individual, social environmental, and cultural factors, we examined how motivational factors and environmental responsiveness were jointly related to college students’ creative achievement in different nations. Participants were university students from eight culturally and geographically diverse regions: Argentina, Austria, Chile, China, Kosovo, Russia, Saudi Arabia, and Turkey. Overall, the results painted a generally positive picture of the relationship between environmental responsiveness, motivational factors, and creative achievement. By employing structural equation modeling (SEM) and multiple-group SEM (MGSEM) methods, results partially supported the mediation role of motivational factors between environmental responsiveness and creative achievement. In addition, we observed more consistent relationships between parental responsiveness and motivational factors or creative achievement, than lecturer. This held in common across all seven countries which fulfilled the requirements for the SEM process, indicating that parents play a potential vital role in supporting students’ motivational aspects and creative achievements, whereas lecturers supporting role is relative to the cultural organizational circumstances. As the first large-scale empirical study with a socio-cultural approach, we invited further discussion and proposed future cross-cultural research of this kind. Research implications and practical suggestions were addressed.
CRIS-Team Scopus Importer:2020-07-24
Keywords: creative achievement; creativity; lecturer responsiveness; motivational factors; parental responsiveness; socio-cultural approach

Social Perceptions of a Creative Person: Stereotypes and Prejudice of a Creative Student among German Adolescents - Zhang, Zhitian; Hopp, Manuel; Vialle, Wilma; Ziegler, Albert (Creativity Research Journal, 2020)
This study builds from the implicit theory of creative individuals to an understanding of the social perceptions of creative individuals. Stereotypes and prejudice about creative students were examined utilizing the self-developed stereotype and prejudice scales among German adolescents. The results indicate that German adolescents hold positive images of creative students, seeing them as competent, warm and popular. Their primary perception of a creative student was admiration, which could be predicted by their stereotypes. In addition, the gender and age effects on adolescents’ social perception were examined. The results show that boys and girls tend to expect the creative student to be the same gender as themselves; and the ratings of stereotype and prejudice in the pre-teens group were significantly higher than in the teens group. These findings provide a refined image of creative individuals from a social perception perspective and partially explain the observed variations due to gender and age factors.
CRIS-Team Scopus Importer:2020-10-30

Soziotope als konstitutive Rahmenbedingungen der MINT-Foerderung von Maedchen und Frauen. Sociotopes ad constitutive framework conditions for promotion of girls and women in domains of mathematics, computer science, sciences, and technology - Ziegler, Albert; Reutlinger, Marold; Hering, Eva Marie (Maedchen und Frauen in MINT. Bedingungen von Geschlechtsunterschieden und Interventionsmoeglichkeiten., 2012)
Keywords: *Educational Programs; *Human Females; *Mathematics; *Participation; *Sciences; *Social Environments; 35]; Bildungsprogramme (focus); Computer Science; Computerwissenschaft; Curricula; Bildungsprogramme und Lehrmethoden [3530; Frauen (focus); Learning Environment; Lernumgebung; Mathematics Education; Mathematik (Wissenschaft) (focus); Mathematikunterricht; Naturwissenschaftlicher Unterricht; Partizipation (focus); Science Education; Soziale Umwelt (focus); Technologie; Technology; Wissenschaften (focus)

Soziotope als konstitutive Rahmenbedingungen der MINT-Förderung von Mädchen und Frauen - Ziegler, Albert; Reutlinger, Marold; Hering, Eva Marie (Mädchen und Frauen in MINT : Bedingungen von Geschlechtsunterschieden und Interventionsmöglichkeiten, 2012)

Soziotope [Special Issue] - Stöger, Heidrun; Ziegler, Albert (Journal für Begabtenförderung, 2016)

Spaces of possibilities: a theoretical analysis of mentoring from a regulatory perspective - Ziegler, Albert; Gryc, Katharina; Hopp, Manuel; Stoeger, Heidrun (Annals of the New York Academy of Sciences, 2020)
A review of the literature on the effectiveness of mentoring reveals a paradox: on the one hand, there is evidence that mentoring can be highly effective. On the other hand, meta-analyses usually only show small to moderate effect sizes, and sometimes even negative effects. To better understand this mentoring paradox, we discuss three fundamental problems in mentoring research. We propose working definitions and theoretical premises to overcome these problems. We apply various systemic concepts to the field of mentoring that might help to resolve the mentoring paradox. We introduce mentees' actiotopes and their interaction with other systems as the unit of analysis, and the regulations for which mentors are responsible for in the context of mentoring as the categories of analysis. To systemize and elaborate on the regulatory dimensions of mentoring, we introduce the nonagonal framework of regulation in mentoring (NFR-M). To facilitate the analysis of ongoing changes caused by mentoring and therefore a dynamic understanding of mentoring, we introduce the concept of spaces of possibilities in mentoring (M-spaces). Finally, we introduce the concepts of the Athena Mentor to explain why mentors can differ so dramatically in the effectiveness of the regulations they are responsible for in the context of mentoring. We conclude by describing how mentoring comparisons based on the NFR-M, mentors' regulatory insight, regulatory power, and M-spaces can help to resolve the mentoring paradox.
CRIS-Team WoS Importer:2020-07-24

Specifying relations between fine motor skills and cognitive abilities: a cross-cultural study - Martzog, Philipp; Chen, Wei; Stöger, Heidrun; Shi, Jiannong; Ziegler, Albert (Talent development and excellence, 2012)

Standards for field evaluations of modifications to educational settings - Ziegler, Albert; Schimke, Diana; Stöger, Heidrun; Merrotsy, Peter (Problems of Education in the 21st Century, 2010)

STEM education for the gifted in Germany - Ziegler, Albert; Händel, Marion (2013)

Stress development during emergency remote teaching in higher education - Obermeier, Ramona; Gläser-Zikuda, Michaela; Bedenlier, Svenja; Kammerl, Rudolf; Kopp, Bärbel; Ziegler, Albert; Händel, Marion (Learning and Individual Differences, 2022)
Higher education includes e-learning in addition to on-site learning. Still, the shift to Emergency Remote Teaching (ERT) as reaction to the Covid-19 pandemic in the summer semester 2020, presented a challenging situation for students. Cross-sectional studies pointed towards higher stress levels of students. However, only a few studies addressed the development of students' stress across several dimensions (joy, worry, tension, demands) within one semester. The current study analyzed trajectories of stress in ERT in relation to age, gender, digital readiness, and experience of loneliness, based on a sample of N = 2795 German students. Latent Growth Curve Models (LGCM) revealed a significant increase in demands, tension and worries and a decrease in joy during the summer term 2020. The development of tension and demands was influenced by age, gender, digital readiness, and loneliness. The decrease in joy and increase in worries could be primarily attributed to digital readiness and loneliness.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Digital readiness; Emergency remote teaching; Higher education; Perceived stress; Social embeddedness

Student perceptions of high-achieving classmates - Händel, Marion; Vialle, W; Ziegler, Albert (High ability studies, 2013)

Successful in Science Education and Still Popular: A pattern that is possible in China rather than in Germany or Russia - Händel, Marion; Duan, X; Sutherland, Margaret; Ziegler, Albert (International journal of science education, 2014)
Across several countries, science is often regarded as unpopular and a male-dominated domain. Furthermore, the number of students who are interested in science education or intend to work in the field of science is relatively low. This might be due to expectations adolescents hold towards science and successful scientists. The current cross-national study investigates the expectations of students in relation to highly achieving peers in science education in the three countries China, Germany and Russia (N=420). Students were asked to indicate their expectations about two fictitious new classmates with respect to three categories: intelligence, social competence and eagerness. Besides national differences, differences concerning the gender of the participating students, the gender of the target students (fictitious highly achieving students in science education) and interaction effects were investigated. Whereas the effects of gender and target gender are inconsistent and negligible, there are significant national differences. Notably, Chinese students hold the most positive expectations about successful peers in science education. The results are discussed with regard to possible explanations and educational consequences.
Keywords: Attitudes; Gender-related; Science; Technology; Society

Systemic gifted education. A theoretical introduction - Ziegler, Albert; Stöger, Heidrun (Gifted child quarterly, 2017)

Systemic gifted education - Ziegler, Albert; Stöger, Heidrun; Balestrini, Daniel Patrick; Phillipson, Shane N; Phillipson, Sivanes (The handbook of secondary gifted education, 2014)
UnivIS-Import:2015-04-20:Pub.2014.phil.dps.ipsy1.lpsych_2.system

Systemische Mädchenförderung in MINT: Das Beispiel CyberMentor - Ziegler, Albert; Schirner, Sigrun; Schimke, Diana; Stöger, Heidrun (Bildungsprozesse im MINT-Bereich : Interesse, Partizipation und Leistungen von Mädchen und Jungen, 2010)
UnivIS-Import:2015-04-20:Pub.2010.phil.dps.ipsy1.lpsych_2.system

Talent denied: Equity and excellence gaps in STEMM - Ziegler, Albert; Stoeger, Heidrun (Annals of the New York Academy of Sciences, 2023)
In principle, there could be STEMM talent everywhere if there were sufficient and adequate opportunities and learning resources everywhere. The reality, however, is that the likelihood of developing one's talent in STEMM is tied to membership in social groups. In this contribution, we explore the implications of this statement with multiple examples for different social groups and for different stages of talent development. We propose an educational framework model for analyzing equity gaps in STEMM talent development that identifies and systematizes the unequal and inequitable distribution of resources and opportunities as the proximal cause of the emergence of such equity gaps. Furthermore, we discuss important aspects for closing equity gaps in STEMM talent development. We argue that-similar to public health approaches-the focus in establishing equity in STEMM talent development should be on prevention rather than intervention. We discuss the importance of the cooperation of societal subsystems and argue for the use of adequate methods of disparity detection for creating equal opportunities. We also outline why preventive strategies are crucial for the creation of resource parity and explain why outcome standards should be considered obligatory.
CRIS-Team Scopus Importer:2023-12-29
Keywords: educational capital; equity gap; learning capital; STEMM; talent denied; talent development; underserved groups

Talent development as adaption: The role of educational and learning capital - Ziegler, Albert; Baker, Joseph (Exceptionality in East Asia : explorations in the actiotope model of giftedness, 2013)

The actiotope model of giftedness: a short introduction to some central theoretical assumptions - Ziegler, Albert; Vialle, W; Wimmer, Bastian (Exceptionality in East Asia : explorations in the actiotope model of giftedness, 2012)

The Development of the Nuremberg Gifted Identification Checklist (NGIC) - Harder, Bettina; Mahn, M; Trottler, Susanne; Ziegler, Albert (3rd International Conference on Talent Development & Excellence (ICTDE), 2013)

The development of the Nuremberg Gifted Identification Checklist (NGIC) - Ziegler, Albert; Harder, Bettina; Mahn, M; Trottler, Susanne (20th Biennial World Conference of the World Council for Gifted and Talented Children (WCGTC), 2013)

The effectiveness of a one-year online mentoring program for girls in STEM - Stöger, Heidrun; Duan, X; Schirner, Sigrun; Greindl, Teresa; Ziegler, Albert (Computers & Education, 2013)

The effectiveness of a one-year web-based mentoring program for girls in STEM - Greindl, Teresa; Schirner, Sigrun; Stöger, Heidrun; Ziegler, Albert (Proceedings of the IADIS International conference Web Based Communities and Social Media, 2013)

The effects of inhibitory control training for preschoolers on reasoning ability and neural activity - Liu, Q; Zhu, X; Ziegler, Albert; Shi, J (Scientific Reports, 2015)

The Hector seminar: A beacon for high-school talent development in STEM school subjects - Ziegler, Albert (Excellence : essays in honour of Kurt A. Heller, 2011)

The impact of beliefs on intelligence, achievement and creativity: Theoretical considerations based on the Actiotope Model of Giftedness - Ziegler, Albert (Gifted education as a lifelong challenge. Essays in honour of Franz J. Mönks, 2012)

The Mentor Perspective: What Makes and Breaks a School-Based Talent Development Mentoring for Youth? - Daunicht, Tina-Myrica; Ziegler, Albert; Stoeger, Heidrun (Tagung experimentell arbeitender Psychologen (TEAP), 2023)

The meta-analyses of deliberate practice underestimate the effect size because they neglect the core characteristic of individualization—an analysis and empirical evidence - Debatin, Tobias; Hopp, Manuel; Vialle, Wilma; Ziegler, Albert (Current Psychology, 2021)
Influential meta-analyses have concluded that only a small to medium proportion of variance in performance can be explained by deliberate practice. We argue that the authors have neglected the most important characteristic of deliberate practice: individualization of practice. Many of the analyzed effect sizes derived from measures that did not assess individualized practice and, therefore, should not have been included in meta-analyses of deliberate practice. We present empirical evidence which suggests that the level of individualization and quality of practice (indicated by didactic educational capital) substantially influences the predictive strength of practice measures. In our study of 178 chess players, we found that at a high level of individualization and quality of practice, the effect size of structured practice was more than three times higher than that found at the average level. Our theoretical analysis, along with empirical results, support the claim that the explanatory power of deliberate practice has been considerably underestimated in the meta-analyses. The question of how important deliberate practice is for individual differences in performance remains an open question.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Deliberate practice; Expertise; Skill acquisition; Talent development

Theoretical approaches, societal issues, and practical implications for school-based and extracurricular talent development: Outcomes of the Inaugural European-North American Summit on Talent Development (Part II) [Guest Editorial] - Stöger, Heidrun; Olszewski-Kubilius, P; Subotnik, R F; Assouline, S; McCouach, D B; Ziegler, Albert (High ability studies, 2017)

Theoretical approaches, societal issues, and practical implications for school-based and extracurricular talent development: Outcomes of the Inaugural European-North American Summit on Talent Development (part I) [Special Issue] - Stöger, Heidrun; Olszewski-Kubilius, P; Subotnik, R F; Assouline, S; McCouach, D B; Ziegler, Albert (Gifted child quarterly, 2017)

Theoretische Perspektiven der modernen Pädagogik - Ziegler, Albert; Zwick, Elisabeth (LIT, 2014)
UnivIS-Import:2015-05-08:Pub.2014.phil.dps.ipsy1.lpsych_2.dynami

Theoretische Perspektiven der modernen Pädagogik - Ziegler, Albert; Zwick, Elisabeth (LIT, 2014)
UnivIS-Import:2015-04-02:Pub.2014.phil.dps.ipsy1.lpsych_2.theore

The paradoxical attenuation effect in tests based on classical test theory: Mathematical background and practical implications for the measurement of high abilities - Ziegler, Albert (High ability studies, 2009)

The significance of learning contexts in talent development - Ziegler, Albert; Grigorenko, Elena L; Harder, Bettina (High ability studies, 2014)

The smarter the more self-regulated? A study on the relationship between intelligence and self-regulated learning - Sontag, Christine; Harder, Bettina; Stöger, Heidrun; Ziegler, Albert (Talent development and excellence, 2012)

The Structure of Social Networks and Its Link to Higher Education Students’ Socio-Emotional Loneliness During COVID-19 - Hopp, Manuel; Händel, Marion; Bedenlier, Svenja; Gläser-Zikuda, Michaela; Kammerl, Rudolf; Kopp, Bärbel; Ziegler, Albert (Frontiers in Psychology, 2022)
Lonely students typically underperform academically. According to several studies, the COVID-19 pandemic is an important risk factor for increases in loneliness, as the contact restrictions and the switch to mainly online classes potentially burden the students. The previously familiar academic environment (campus), as well as the exchange with peers and lecturers on site, were no longer made available. In our cross-sectional study, we examine factors that could potentially counteract the development of higher education student loneliness during the COVID-19 pandemic from a social network perspective. During the semester, N = 283 students from across all institutional faculties of a German comprehensive university took part in an online survey. We surveyed their social and emotional experiences of loneliness, their self-reported digital information-sharing behavior, and their current egocentric networks. Here, we distinguished between close online contacts (i.e., mainly online exchanges) and close offline contacts (i.e., mainly in-person face-to-face exchanges). In addition, we derived the interconnectedness (i.e., the densities of the egocentric networks) and heterogeneity (operationalized with the entropy) of students’ contacts. To obtain the latter, we used a novel two-step method combining t-distributed stochastic neighbor embedding (t-SNE) and cluster analysis. We explored the associations of the aforementioned predictors (i.e., information-sharing behavior, number of online and offline contacts, as well as interconnectedness and heterogeneity of the close contacts network) on social and emotional loneliness separately using two hierarchical multiple linear regression models. Our results suggest that social loneliness is strongly related to digital information-sharing behavior and the network structure of close contacts. In particular, high information-sharing behavior, high number of close contacts (whether offline or online), a highly interconnected network, and a homogeneous structure of close contacts were associated with low social loneliness. Emotional loneliness, on the other hand, was mainly related to network homogeneity, in the sense that students with homogeneous close contacts networks experienced low emotional loneliness. Overall, our study highlights the central role of students’ close social network on feelings of loneliness in the context of COVID-19 restrictions. Limitations and implications are discussed.
CRIS-Team Scopus Importer:2022-02-11
Keywords: COVID-19 pandemic; digital information-sharing behavior; interconnectedness; loneliness; network density; network heterogeneity; network homogeneity; social network

The Supporting Role of Mentees’ Peers in Online Mentoring: A Longitudinal Social Network Analysis of Peer Influence - Hopp, Manuel; Stoeger, Heidrun; Ziegler, Albert (Frontiers in Psychology, 2020)
Studies show that online mentoring is an effective measure to support girls in STEM (science, technology, engineering, and mathematics), especially if it also allows for networking with other participants on the mentoring platform. However, research is missing on peer influence. This topic seems especially crucial in programs for adolescents as peer influence plays an important role at this age. In our study, we investigated peer influence on mentoring outcomes – confidence in own STEM abilities and STEM-related activities – in an online mentoring program in STEM for secondary school girls (N = 124, M = 14.3 years, SD = 2.2 years, age range: 11–19 years). The program provides girls with at least 1 year of one-on-one interaction with a personal female mentor who has a college degree in a STEM subject. Participants can also interact with other participants on the platform. We used a longitudinal social network analysis approach to examine peer influence on mentoring outcomes. Our results indicate that both mentoring outcomes – mentees’ confidence in own STEM abilities and STEM-related activities – are influenced by peers moderated by the mentees’ own age. Younger mentees tended to become more similar to their peers regarding confidence in own STEM abilities and STEM-related activities, whereas older mentees tended to become more dissimilar over time. In addition, peer group size had a positive effect on confidence in own STEM abilities, but not on STEM-related activities. This effect was moderated by the mentee’s age. Overall, peers have a positive influence on the measured mentoring outcomes, especially for young mentees.
CRIS-Team Scopus Importer:2020-09-11
Keywords: online mentoring; peer influence; RSiena; social network analysis; STEM

The tower of creativity - Ziegler, Albert; Vialle, W (Cultivation and Education of Creativity, 2009)

The webcam and student engagement in synchronous online learning: visually or verbally? - Händel, Marion; Bedenlier, Svenja; Kopp, Bärbel; Gläser-Zikuda, Michaela; Kammerl, Rudolf; Ziegler, Albert (Education and Information Technologies, 2022)

Towards a systemic theory of gifted education - Ziegler, Albert; Phillipson, Shane N (High ability studies, 2012)

Towards Exceptionality: The Current Status and Future Prospects of Australian Gifted Education - Phillipson, Shane N.; Ziegler, Albert (Handbook of Giftedness and Talent Development in the Asia-Pacific, 2021)
In this chapter some challenges currently facing gifted education in Australia will be identified, and we will outline what we believe are its future prospects. To better understand these challenges, however, it is important to place gifted education within a broader educational context, including a discussion of Australian gifted education policy and Australian research into gifted education. We argue that, at best, the relevance of gifted education is being undermined by what can be described as a ‘crowded classroom’. We conclude that in order to ensure that the needs of Australian students with the potential for exceptional achievement are met, gifted education must evolve in the way it defines giftedness and implements gifted education. This evolution must take advantage of the current regulatory environment, beginning with a National Policy that focuses on the development of exceptionality, supported by a systems-based model of talent development, that is, the actiotope model.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Actiotope model; Australia; Evaluation; Gifted education; Policy

Two studies of the empirical basis of two learning resource-orientated motivational strategies for gifted educators - Vladut, Anamaria; Vialle, Wilma; Ziegler, Albert (High ability studies, 2016)

Underachievement - Ziegler, Albert; Stöger, Heidrun (Begabungsförderung und Schulentwicklung, 2009)
UnivIS-Import:2015-04-20:Pub.2009.phil.dps.ipsy1.lpsych_2.undera

Underachievement: Ein kritischer Review - Ziegler, Albert; Stöger, Heidrun (ECHA Österreich : ein Markenzeichen für Begabungsförderung und Schulentwicklung, 2009)

Verschiedene Stichwortbearbeitungen (Aktiotop, Soziotop, Bildungskapital etc.) - Ziegler, Albert (2013)

von CyberMentor zu CyberMINT-Communities: Acht Jahre erfolgreiche MINT-Mädchenförderung - Stöger, Heidrun; Ziegler, Albert; Buschhaus, F; Greindl, Teresa; Groß, C; Heilemann, M; Hopp, Manuel; Meierhofer, Tanja; Schirner, Sigrun; Sturm, K; Teuffenbach, V; Werner, K; et al. (Druck Team, 2014)
UnivIS-Import:2015-04-02:Pub.2014.phil.dps.ipsy1.lpsych_2.voncyb

Why Experts Can Do What They Do: The Effects of Exogenous Resources on the Domain Impact Level of Activities (DILA). - Debatin, Tobias; Hopp, Manuel; Vialle, Wilma; Ziegler, Albert (Psychological Test and Assessment Modeling, 2015)
In many domains, it is estimated that approximately 10,000 hours of planned learning activities are required to reach an expert level of performance. However, this poses a challenge for learners to balance such extensive learning times with the demands of everyday life. In our study we focused on activities in the domain of chess. We hypothesized that chess-related activities could be better integrated in an individual’s life if exogenous resources – specified in the educational capital approach (Ziegler & Baker, 2013) – are sufficiently available. In order to test this hypothesis we introduced the concept of the Domain Impact Level of Activities (DILA), that is, the degree to which a learner's activities are influenced by a certain domain. As expected, we found that the more exogenous resources (educational capital) chess players had at their disposal, the higher was their DILA in regard to social and everyday activities. Concerning social activities, we also found a direct effect of playing time hours and a small indirect effect of educational capital on the DILA via playing time hours. In the model predicting the DILA of everyday activities, these effects were not found. It was concluded that the availability of educational capital facilitates the integration of domain-related activities in a learner’s life.
Keywords: Educational capital; actiotope; chess; expertise

Wie begehrt sind Hochbegabte Jungs bei Mädchen und umgekehrt? - Basar, D; Berger, K; Fidelman, Marina; Finkenzeller, F; Friedrich, D; Gesell, J F; Hübner, P; Meyer, K; Reutlinger, Marold; Seibold, F; Wunderlich, K; Ziegler, Albert (News & science, 2010)

Wie effektiv ist Mentoring? Ergebnisse von Einzelfall- und Meta-Analysen - Stöger, Heidrun; Ziegler, Albert (Diskurs Kindheits- und Jugendforschung, 2012)

Wie gestresst sind Lehramtsstudierende im Kontext der Umstellung auf digitale Lehre? - Obermeier, Ramona; Gläser-Zikuda, Michaela; Bedenlier, Svenja; Kammerl, Rudolf; Kopp, Bärbel; Ziegler, Albert; Händel, Marion (Lehrerbildung auf dem Prüfstand, 2021)

Wie gestresst sind Lehramtsstudierende im Kontext der Umstellung auf digitale Lehre? - Obermeier, Ramona; Gläser-Zikuda, Michaela; Bedenlier, Svenja; Kopp, Bärbel; Kammerl, Rudolf; Ziegler, Albert; Händel, Marion (Lehrerbildung auf dem Prüfstand, 2021)
Bedingt durch die Covid-19-Pandemie wurde das Sommersemester 2020 deutschlandweit als reines Digital-Semester aufbereitet. Dies stellte Hochschulen, Lehrende und Studierende vor große Herausforderungen. Lehramtsstudierende, die der Nutzung digitaler Medien tendenziell eher skeptisch gegenüberstehen, sich studienbedingt aber mit (medien)-didaktischen und -pädagogischen Fragen beschäftigen, stellen dabei eine Zielgruppe von besonderem Forschungsinteresse dar. Die vorliegende Studie thematisiert das Stresserleben von Lehramtsstudierenden im Zuge der Umstellung auf digitalisierte Lehre im Sommersemester 2020. Dabei werden unterschiedliche Voraussetzungen auf Studierendenseite (z. B. Medienkompetenz) und durch die Umstellung auf digitale Lehrangebote bedingte Faktoren, wie eine geringere soziale Eingebundenheit, berücksichtigt. Die Ergebnisse längsschnittlich erfasster Daten von N = 51 Studierenden des Grund- und Mittelschullehramts einer Hochschule zeigen eine Zunahme im Stresserleben im Digital-Semester. Die Befunde unterstreichen ferner die Bedeutung der erlebten sozialen Eingebundenheit für diese Entwicklung. Wenngleich die Studie aufgrund ihrer geringen Stichprobengröße eingeschränkt ist, liefert sie wichtige Erkenntnisse in der speziellen Situation der ad-hoc Umstellung der Hochschullehre, die auch für weitere Digitalisierungsprozesse des Lehramtsstudiums genutzt werden könne
Keywords: E-Learning; Lehrerbildung; Medienkompetenz; soziale Eingebundenheit; Stresserleben

Wo steht die Mentoringforschung im Hype-Zyklus? Resultate eines Lite- raturüberblicks - Ziegler, Albert; Schimke, Diana; Stöger, Heidrun (Mentoring : Theoretische Hintergründe, empirische Befunde und praktische Anwendungen, 2009)

Wo steht Mentoring: Ein Überblick - Ziegler, Albert; Stöger, Heidrun; Schimke, Diana (Mentoring: Theoretische Hintergründe, empirische Befunde und praktische Anwendungen, 2009)
UnivIS-Import:2015-04-20:Pub.2009.phil.dps.ipsy1.lpsych_2.wosteh

Zur Bedeutung der Begriffe Begabung, Talent und Hochbegabung: Ergebnisse einer korpuslinguistischen Analyse - Balestrini, Daniel Patrick; Harder, Bettina; Stöger, Heidrun; Ziegler, Albert (News & science, 2014)